Insights into the suppression of filamentous bulking by quorum quenching in the activated sludge process with low dissolved oxygen: Endogenous quorum quenching mediated multi-enzymatic degradation of AHLs and carbon-flux redistribution - Peng Zhang; Yi Fu; Hong-Xin Shi; Jin-Song Guo; You-Peng Chen; Peng Yan (Bioresource Technology, 2027)

Engineered lipase enables selective hydrolysis of palmitic over oleic acyl chains at a two‑phase microfluidic interface - Jin-Zheng Wang; Lu Tan; Cheng-Kun Wu; Xin-Ying Wang; Kheng Lim Goh; Richard Ansah Herman; Shuai You; Sheng Sheng; Fu-An Wu; Jun Wang (Bioresource Technology, 2026)

Petrogenesis of the middle Jurassic Luorong syenite and Xishan A-type granite in the southern Qin-Hang belt, South China: Implications for contrasting mixed sources and divergent differentiation pathways - Zheng-Wei Qin; Xi-Yao Li; Wolfgang Siebel; Jian-Ming Fu; Sanzhong Li; You-Yue Lu; Yu-Xiao Yao; Yu-Shuai Yu; Bo Bao (Journal of Asian Earth Sciences, 2026)

Assessing the cardiovascular toxicity of aspartame: An integrated approach from computational prediction to experimental validation - Qiuhe Chen; Hongjing You; Hecai Wang; Xuanchen Guan; Xiujuan Cen; Lanting Fu; Liang Long; Ke Wang; Yue Xu; Yang Chen (Chemico-Biological Interactions, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Ebselen inhibits PRRSV replication by activating the TRIM16/SQSTM1–KEAP1–NRF2-mediated oxidative stress response pathway - Xinrong Wang; Yan Guo; Linjie Hou; Lingqiao You; Qing Zhang; Junhai Zhu; Longxiang Zhang; Nan Yan; Jun Lu; Lizhi Fu; Yue Wang (Veterinary Microbiology, 2026)

Integrative taxonomic revision of Uropsilus (Uropsilinae, Talpidae) combining genomic, morphological and geographic evidence - Yi-Xian Li; Quan Li; Wen-Yu Song; Xue-You Li; Kenneth Otieno Onditi; Xiao-Xin Pei; Hong-Jiao Wang; Chang-Kun Fu; Shao-Ying Liu; Zhong-Zheng Chen; Xue-Long Jiang (Molecular Phylogenetics and Evolution, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Physicochemical pretreatment for enhancing anammox and related coupled processes in the treatment of high-strength ammonium industrial wastewater: Research advances and prospects - Long Jiao; Xue-chao Wang; Jia-lin Xue; Zhuo-yuan You; Jie Li; Jia-jun Fu; Hong Yu (Journal of Environmental Chemical Engineering, 2026)

Ultrasound-microwave synergistic treatment modulates highland barley dough structure and bread quality characteristics - Xiaolu Wu; Liping Fu; Xinyi Chen; Sizhe You; Wenhui Zhang; Liangfeng Ma; Qisen Xiang; Yuting Tian; Yingting Zhao (Food Research International, 2026)

A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

Electrolytic Manganese Residue (EMR): A Review on Harmless Treatment, Resource Utilization, and Emerging Technologies - Duo Wu; You Cheng; Haoze Zhang; Xiuli Yang; Jiening Huang; Tao Fu (International Journal of Environmental Research, 2026)

Occurrence and risk assessment of benzotriazole UV stabilizers in a major drinking water reservoir by target, suspect, and nontarget screening analysis - Yuting Dong; Rifu You; Mingliang Liu; Xueqin Wei; Jie Fu; Guohua Zhu; Guogan Peng; Kai Huang; Bao Zhu; Pengyang Li; Haiyan Zhang; Aiqian Zhang; et al. (Water Research, 2026)

Wetting-induced collapse of loess: Multistage microstructural evolution of particles and pores - Longlong Lv; Yaoxing You; Yukuai Wan; Yingpeng Fu (Transportation Geotechnics, 2026)

A fully human antibody A140 neutralizes abrin toxin via lysosomal intracellular mechanisms, confers potent protection in vitro and in vivo, and reverses transcriptomic dysregulation with a Favorable safety profile - Feng Qin; Shi-You Chen; Peng Lin; Bin Wang; Xin Fu; Jian-Li Jiang; Hong-Yong Cui; Shi-Jie Wang (Toxicology and Applied Pharmacology, 2026)

How phosphorus enrichment regulates the microbial community resistance and multifunctions tolerance to drying–rewetting cycles in paddy fields: the critical role of stoichiometry - Jiaying Wang; Yi Xu; Tinghong Fu; Guoxiang You; Rui Wang; Tianyun Li; Zewei Jiang; Shihong Yang (Journal of Environmental Management, 2026)

Facile formation of zein microbeads integrated with a plant protein-based bioink for cultivated meat texturization - Linzhi Jing; Lingshan Su; Siyong You; Shunjiang Zeng; Zihan Zheng; Yanfei Xu; Yafang Ma; Jia Gu; Tiange Liu; Zhao Liu; Caili Fu; Yan Kong; et al. (Food Hydrocolloids, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Low-dose arsenate promotes high-efficiency anammox: From granular properties to synergistic metabolism - Que Wang; Xiao-Wei Xu; Zhang-Yi Wang; Hong-Yuan Liu; Lei Wang; Hui-Ming Fu; Ya-Min Liu; Peng Yan; Ling-Ling Wang; You-Peng Chen (Chemical Engineering Journal, 2026)

Titanate-functionalized separator enables an in-situ redox reaction toward intrinsically dendrite-free aqueous zinc-ion batteries - Tong Jiang; You Fu; Zhenyu Wang; Siqinhaolu Hao; Yaxin Li; Zilong Liu; Mingjie Jia; Yongjian Ai; Yinggang Jia; Guangwen Xu; Hong-bin Sun (Chemical Engineering Journal, 2026)

Ultrahigh-resolution flexible quantum-dot light-emitting diodes via dual assembly and transfer printing - Xin Hu; Yangbin Zhu; Runzhen Sun; Zhen Wang; Jiayu Sun; Qinghong Lin; Yi Jiang; Hongyang Fu; Kejia You; Xuan Guo; Yue Wang; Deli Li; et al. (Chemical Engineering Journal, 2026)

A chitosan-based cinnamaldehyde–raspberry ketone integrated carrier architecture for oral delivery toward mild metabolic regulation - Yu-Chi Wang; Sin-Huei Chuang; Chien-Fu Lin; Yan-Ting Lin; You-Song Cheng; Chih-Chen Lin; Chi-Chen Ting; Wei-Han Chen; Ting-Yu Chen; Shen-Ho Kuo; Fu-I Tung; Tse-Ying Liu (Carbohydrate Polymers, 2026)

Vegetable waste into soil acts as slowly released water and fertilizer to improve current vegetable productivity with less chemical fertilization - Adnan Khan; Ling Zhao; Jing Wang; Yun-Li Xiao; Jian-Ming Li; Hua-Guo Zhu; Shi-Sheng Li; Meng-Ying Li; Habimana Evode; Chang Nan; Muhammad Ashraf; Fu-Jian Mei; et al. (Bioresource Technology, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

New linear bromopyrrole-imidazolidine alkaloids from the Formosan sponge Agelas nakamurai - You-Cheng Lin; Atallah F. Ahmed; Chung-Wei Fu; Shu-Fen Chiou; Hui-Chun Wang; Ping-Jyun Sung; Jyh-Horng Sheu (Natural Product Research, 2026)

Retraction notice to “Rapid transition of aerosol optical properties and water-soluble organic aerosols in cold season in Fenwei Plain” [Sci. Total Environ. 829 (2022) 154661] - Aodong Du; Yan Li; Jiaxing Sun; Zhiqiang Zhang; Bo You; Zhijie Li; Chun Chen; Jie Li; Yanmei Qiu; Xingang Liu; Dongsheng Ji; Wenjie Zhang; et al. (Science of The Total Environment, 2026)

Multi-omics analysis of the rhizosphere effects and molecular mechanisms of Ageratum conyzoides linn. at different stages of Cd, Pb, and Zn co-stress - Yuexin Fu; Mouyixing Chen; Xuehong Zhang; Guo Yu; Pingping Jiang; Jie Liu; Shaohong You (Journal of Environmental Management, 2026)

Structural performance of rectangular CFST slender columns under axial partial compression - You-Fu Yang; Feng Fu (Engineering Structures, 2026)

CRISPR-Cas12a-coupled split-promoter activator bridge enables reusable one-reporter-multiple-target cell-free nucleic acid diagnostics - Fengling Fang; Mingming Zhao; Weiquan You; Xiangjun Tang; Shanjian Chen; Yao Yin; Qishui Ou; Yueguo Li; Ya Fu (Chemical Engineering Journal, 2026)

Lithological controls on clustered landslides: a case study of landslides triggered by Typhoon Gaemi (2024) in Zixing, Hunan Province, China - Qi You; Fawu Wang; Hao Ma; Zijin Fu; Youqian Feng (Landslides, 2026)

A CNN–Transformer hybrid network for efficient cross-region landslide detection by transfer learning - Zijin Fu; Fawu Wang; Junfei Zhong; Filippo Catani; Jie Dou; Qi You; Bo Zhang (Landslides, 2026)

Identification of suitable habitats for the six-spotted mite on rubber trees using multi-source data and MaxEnt modeling - Yanan You; Huichun Ye; Donghua Wang; Chaojia Nie; Jingjing Wang; Bingsun Wu; Fengzheng Cai; Jiajian Deng; Lixia Shen; Fu Wen (Experimental and Applied Acarology, 2026)

Cardiovascular toxicity of ethyl maltol exposure: a comprehensive investigation from virtual screening to experimental validation - Qiuhe Chen; Lanting Fu; Hecai Wang; Xiujuan cen; Liang Long; Hongjing You; Qimeng Tan; Xinyue Chen; Yuhao Liu; Haiyan Li; Yue Xu; Yang Chen (Archives of Toxicology, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Thermal Tolerance of Geographical Populations and Their Hybrids in the Ivory Shell Babylonia areolata - Jingqiang Fu; Linwei Nie; Zhenzhen Cai; Weiguang Zou; Yuan Liang; Wengang Lü; Minghui Shen; Xuan Luo; Weiwei You; Tuanyu Guo; Caihuan Ke (Fishes, 2026)
Global warming and summer heatwaves increasingly threaten the survival of cultured Babylonia areolata, but the heat tolerance of different geographical populations and the potential for genetic improvement by hybridization remain poorly understood. In this study, four geographical populations (Thailand, TL; Wanning, WN; Zhao’an, ZA; Changle, CL) and four hybrid combinations (TH, HT, TF, and FT) were compared for mortality rate, median lethal temperature (LT50), and critical thermal maximum (CTMax) under controlled thermal stress. The results showed that the low-latitude TL population exhibited significantly higher LT50 (36.49 ± 0.05 °C) and CTMax (35.77 ± 0.52 °C) than the high-latitude CL and ZA populations (LT50: 35.90 ± 0.05–36.02 ± 0.04 °C; CTMax: 35.12 ± 0.77–35.26 ± 0.53 °C). All four hybrids had improved heat tolerance compared with their low parents, with TH and HT showing the strongest mid-parent heterosis (e.g., 73.68–78.94% for survival at 36.5 °C). However, none significantly exceeded the high-parent performance (TL), indicating only mid-parent heterosis. These findings reveal significant genetic variation in heat tolerance among geographical populations of B. areolata and confirm that cross-breeding can effectively enhance heat tolerance, though it does not produce transgressive superiority. This study provides key genetic resources and a theoretical basis for breeding heat-tolerant strains of B. areolata.

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

Impact of isolated mountains on groundwater hydrochemical evolution: insight from isotopic and geochemical analysis - Aoao Du; Fu Liao; Yourang Zan; Ziwen Zhang; Bingchao Yang; Xiangzhi You; Qingming Zeng; Guangcai Wang (Journal of Hydrology, 2026)

Dependencies of ecological drought on climatic drivers in diverse ecosystems: Implications for water resources management - Zhiwen You; Leying Fu; Huaiwei Sun; Xuan Ban; Yubo Li; Pengsheng Li; Qiming Zheng; Changqing Meng; Jie Xue; Hui Qin (Journal of Environmental Management, 2026)

Corrigendum to “Photophysical and chiroptical properties of a pair of chiral europium(III) enantiomers with a record external quantum efficiency” [Chem. Eng. J. 537 (2026) 176281] - Qian Xu; Jipeng Fu; Tingyu Gu; Xiaoyang Xia; Tianyi Sun; Kaina Wang; Mingxue Tang; Liang Zhou; You-Xuan Zheng (Chemical Engineering Journal, 2026)

Context-dependent links between microbial co-occurrence topology and nitrogen mineralization in two adjacent subalpine Picea asperata stands - Lixia Wang; Haoying Gao; Shuangjia Fu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; Zhenfeng Xu (Plant and Soil, 2026)

A global meta-analysis of forest edge effects on arthropod abundance and richness - Fu Shi; Weibin You; Xiaolei Huang (Agriculture, Ecosystems & Environment, 2026)

Environmental filtering and serial discontinuity interactively shape macrobenthic metacommunity assembly along the regulated Oujiang River, China - Genting Yu; Jihong Xia; Xinyan Zhou; Qiaoxi Zheng; Weijie Cao; Aiju You; Hui Wu; Lei Fu; Jingwen Hu; Lei Hua; Hongqing Zhang; Yongshu Zhu (Aquatic Sciences, 2026)

Light-driven community assembly and functional performance of aeration-free filamentous algae–partial nitrification/anammox granule - Cui-Zhong Chen; Hui-Min Fu; Tong-Xu Li; Xiao-Yu Gao; Qing Hu; Peng Yan; Jin-Song Guo; Xiao-Wei Xu; You-Peng Chen (Water Research, 2026)

Shear performance of prefabricated utility tunnel joints considering the effect of connectors - Chao Zhang; Jiao-jiao Chen; Wei-ning Zhong; Xin Li; Chen-chen Sun; You-jun Xu; Xin Han; Jun-yi Gao; Jian-jun Wang; Zhi-qiang Fu (Tunnelling and Underground Space Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Transformation and transport: Polyvinyl chloride microplastics modulate fipronil accumulation and toxicity in zebrafish - Long Fu; Jing Yu; Kunting Li; Peibin Xu; Keran Xu; Lei Mai; Dali Wang; Huizhen Li; Jing You; Eddy Y. Zeng (Journal of Environmental Sciences, 2026)

The dual origin of granites from fluid-absent and fluid-fluxed melting of the juvenile lower crust: New constraints from Mo isotopes and phase equilibrium modeling - You-Shan Xia; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Yao Zhou; Zhen-Xin Li; Gang Wen; Lei Qin (Geochimica et Cosmochimica Acta, 2026)

Photophysical and chiroptical properties of a pair of chiral europium(III) enantiomers with a record external quantum efficiency - Qian Xu; Jipeng Fu; Tingyu Gu; Xiaoyang Xia; Tianyi Sun; Kaina Wang; Mingxue Tang; Liang Zhou; You-Xuan Zheng (Chemical Engineering Journal, 2026)

A Compact, Universal Fusion Tag Enables Robust Expression of Challenging Enzymes for Starch Bioconversion and Optimized Metabolism in Bacillus subtilis - Yuqiao Wang; Jinlong Li; Wenhui You; Xuyang Huang; Miaomiao Xia; Jing Qiao; Tao Cai; Ziqing Gao; Gang Fu; Dawei Zhang (Bioresource Technology, 2026)

Integrated identification, quantification, and histopathological characterization of Vibrio spp. associated with disease in juvenile yellowfin tuna (Thunnus albacares) - Yuzhuo You; Zhengyi Fu; Tao Zhang; Jing Hu; Zhenhua Ma; Gang Yu (Aquaculture International, 2026)

Two new compounds from the roots of Paeonia lactiflora Pall. and their anti-inflammatory effects - Bo Fu; Jin-Ling Zhang; Jia-Tong Wu; Si-Yi Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Zhi-Chao Hao; Hai-Xue Kuang; Qing-shan Chen; Li-Li Zhang; Bing-You Yang; et al. (Natural Product Research, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Extreme load assessment and pitch control strategy for floating wind turbines considering the coupled effects of typhoon stage evolution and yaw error - Xiang Wang; Xu Liang; Peng You; Baoxuan Wang; Yue Chen; Fu Li; Bo Ye; Xianhui Zhu (Ocean Engineering, 2026)

A comprehensive flavor evaluation method for drinking water based on flavor rating assessment (FRA) and the flavor wheel, incorporating benchmark referencing and objective weighting - You Lyu; Huan He; Zhen-Ning Luo; Tian-Yang Zhang; Xin-Li Huang; Zhu Peng; Qi Fu; Xin-Bai Jin; Bin Xu (Journal of Water Process Engineering, 2026)

Activation of permanganate(VII) with percarbonate for enhanced oxidation of ciprofloxacin: Sustained generation of manganese intermediates - Xiang Li; Lei Fu; Hui Wu; Aiju You; Pengcheng Yao; Yufei Shi (Desalination, 2026)

5-Aza-CdR increases expression of the tight junction protein ZO-1 via upregulation of miR-126 through promoter hypomethylation in HMEC-1 cells - Xi Zhang; Shaohan Zhang; Yuzhi Shao; You Liu; Kerui Gong; Chunyang Zhang; Zhijun Zhao; Xuguo Ma; Gang Fu; Guo Shao (Tissue and Cell, 2026)

Two new aromatic meroterpenoids from the fruiting bodies of Ganoderma calidophilum - Wei Liu; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Phytochemistry Letters, 2026)

Impacts of rainfall runoff on algal community in a humid region reservoir riverine zone - Cunli Li; Miao Yang; Aiju You; Guangwei Zhu; Ping Zhang; Qiaoxi Zheng; Mengyuan Zhu; Linxing Tu; Hongqing Zhang; Lei Fu; Bin Wang; Jinwen Hu; et al. (Journal of Environmental Chemical Engineering, 2026)

Potential role of AHL-mediated quorum sensing in filamentous bulking induced by Sphaerotilus natans in the activated sludge process with low dissolved oxygen - Yi Fu; Wei-Xin Liu; Shao-Yang Liu; You-Peng Chen; Song-Ya Li; Fang Fang; Jin-Song Guo; Peng Yan (Journal of Environmental Chemical Engineering, 2026)

Preparation of sustainable high-performance grouting material developed with high volume solid waste - You Fu; Haiqiang Jiang; Zhuoran Wang; Bingrui Chen; Sunqiang Yu; Xiaopeng Li (Journal of Environmental Management, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Acute Total Ammonia Nitrogen (TAN) stress affects the skin metabolism, antioxidant capacity, immune function, and tissue structure of juvenile yellowfin tuna (Thunnus albacares) - Yuzhuo You; Wei Wang; Zhengyi Fu; Zhenhua Ma (Fish Physiology and Biochemistry, 2026)

Stepwise biofabrication of CuMnS from electroplating wastewater: bimetal-sulfur synergy for enhanced peroxymonosulfate activation - Xian-Zhong Fu; Yong-Qiang Ma; Xiao-Jing Zhao; Wen-Hui Xu; Chen-Xuan Li; Chun-Yan Guo; Xue-Yuan Wang; Fei-Yang Wang; You-De Zhang; Kang-Ping Cui (Bioresource Technology, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Maritime aerial object detection via dual-domain contrastive learning and low-light degradation enhancement - Liwen Liu; Jiayi Xu; Gui Fu; Xiaoqiang Zhang; You Wang; Rong Fan (Frontiers in Marine Science, 2026)
The expansion of marine economic activities and the increasing demand for maritime security have positioned drone-based aerial object detection as a crucial technology for applications such as marine environmental monitoring and maritime law enforcement. However, maritime aerial imagery remains highly challenging due extreme illumination variations, the small size and indistinct appearance of targets. This paper introduces a novel dual-domain contrastive learning framework integrated with low-light degradation enhancement to address these challenges. First, a low-light degradation perception module performs illumination equalization, improving image uniformity under adverse lighting conditions. Then, a dual-domain contrastive learning strategy aligns representations across both image and feature domains, enabling the detection network to learn more discriminative features. Additionally, a Local Feature Embedding and Global Feature Extraction Module (LEGM) is incorporated into the detection network to enhance the representation of small-scale maritime targets. Experiments on SeaDronessee and AFO datasets demonstrate the superiority of the proposed approach, achieving an improvement of 4.3% in mAP@0.5 and 1.9% in mAP@0.5:0.95 on SeaDronesSee, 1.9% in mAP@0.5 and 1.1% in mAP@0.5:0.95 on AFO. These results confirm that the proposed method delivers robust and accurate maritime object detection under complex environmental conditions and has strong potential for deployment in real-world maritime surveillance applications.

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Study on the thermal insulation efficiency and ecological conservation effects of intelligent sustainable green walls - Hsiao-ling Lu; Yuan-Hsiou Chang; Tsai-Fu Chuang; You-En Zhong; Zhi-Jia Feng (Energy and Buildings, 2026)

Graph-based visual analysis for HVAC system anomaly detection - Tianyuan Cao; Yunzhe Wang; Qiming Fu; You Lu; Jianping Chen; Yushi Li; Chengtao Ji (Energy and Buildings, 2026)

2-Aminoethoxydiphenyl borate induces arrhythmias via Cx43-S282 dephosphorylation - Hongjie You; Lingxi Zhang; Yimeng Zhang; Zhiping Fu; Dali Luo (In Vitro Cellular & Developmental Biology - Animal, 2026)

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Comparison of cancer risks associated with JAK inhibitors and TNF inhibitors treatment in patients with rheumatoid arthritis: a systematic review and meta-analysis of real-world cohort studies - Fu-Yu Yang; Yu-Chang Liu; Min-You Wu; Yao-Cheng Wu; Cheng-Hsien Hung (Inflammation Research, 2026)

Cochliomycin H, a new 12-membered resorcylic acid lactone from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Jiu-Jiu Zhou; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; You-Hua Liu; Zhao You-Xing (Natural Product Research, 2026)

Polyprenylated xanthones with potential anti-inflammatory and anti-HIV effects from the stems and leaves of Cratoxylum cochinchinense (Lour.) Blume - Yong Zhang; You-Di Rao; Jing-Su Yu; Jia-Yi Hu; Wen-Hui Hu; Shu-Ri Li; Hui Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Computer vision-assisted sorting and selective cultivation of high-activity anammox granules - Shi-Jun Li; Haoran Li; Hui-Min Fu; Yi-Cheng Wang; Xun Weng; Wei Wang; You-Peng Chen (Water Research, 2026)

Plant-based edible emulsion gels from rye secalin for 3D-printed fat mimetics - Siyong You; Weitong Wen; Yuhan Wan; Lingshan Su; Shunjiang Zeng; Yan Kong; Caili Fu; Dejian Huang; Linzhi Jing (Food Research International, 2026)

Pseudocapacitive Fe4N nanoparticles encapsulated within interconnected graphene cavities as efficient binder-free capacitive deionization anodes - Liyan Liu; Shaojie You; Wenjun Fu; Jihui Cao; Zhengxin Ding; Chao Xu (Desalination, 2026)

Anammox community characteristics and stable relationships centered on anammox bacteria - Yi-Cheng Wang; Hui-Min Fu; Hong-Yuan Liu; Han Wu; Zi-Han Zeng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; Liang Zhang; You-Peng Chen (Chemical Engineering Journal, 2026)

Ectomycorrhizal exploration types shape soil enzyme activity, decomposition, and nitrogen dynamics in subalpine forests - Lixia Wang; Haoying Gao; Shuangjia Fu; Huichao Li; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Jiao Li; Bo Tan; et al. (Plant and Soil, 2026)

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Review of Sargassum thunbergii (Fucales, Phaeophyta): phycology, chemistry, bioactivity, and application - Xueyu Wang; Dandan Xiao; In-Kyu Yeo; Lei Wang; Yiqiao Li; Jia Fu; Yunhua Fu; Suengmok Cho; You-Jin Jeon; Fengqi Yang (Algae, 2025)
Sargassum thunbergii is a large brown seaweed endemic to the Northwest of Pacific Ocean, widely distributed in the warm temperate coastal waters of South Korea, China, and Japan. It is abundant in resources and has a long history of application, widely used in food, medicine, and feed. In recent years, it has also been used to restore marine ecology. To date, only one review has been published on Sargassum thunbergii aquaculture. Therefore, by investigating the international definitive data repository (ScienceDirect, PubMed, Web of Science, ACS Publications, Springer, etc.) and collecting 92 kinds of literature closely related to phycology, chemistry, biological activity, and applications, herewith a comprehensive and systematic summary and exposition, enveloping the classification and distribution, botanical characteristics, and physiological and biochemical differences of Sargassum thunbergii ; involving 7 chemical classifications of 117 derivatives substances embracing 12 new and 6 first-isolated excluding polysaccharides; mainly including 11 types of pharmacology in vivo and in vitro; evaluating the potential applications related on medicine, healthcare, aquaculture, and marine restoration. This review is expected to provide forward-looking scientific perspectives and act as a valuable reference for future studies, development, and utilization of Sargassum thunbergii .

Groundwater depletion in China’s Granary: The unintended consequences of cropping pattern shifts - Yiqun Shang; Jinwei Dong; Ping Fu; Nanshan You; Xi Zhang; Yuanyuan Di; Yan Zhou; Xi Chen; Zhichao Li; Xinqi Zheng (Journal of Hydrology, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

Highly reversible and stable zinc anodes enabled by a silane self-assembled molecular layer - Chaolin You; Wenjie Zhang; Yi Peng; Weijia Fan; Qi Zhou; Xiaosong Xiong; Lili Liu; Lijun Fu; Yuping Wu (Chemical Engineering Journal, 2025)

Interfacial water layer modulation for efficient photocatalytic CO2 reduction - Jingyi Pang; Hang Zhou; Zejiang Huang; Xiaomeng You; Beibei Xu; Xiaobin Fu; Yilong Weng; Xue-Lu Wang; Ye-Feng Yao (Chemical Engineering Journal, 2025)

Bioequivalence evaluation of dexamethasone palmitate injections by intravenous injection in healthy Chinese volunteers: a 2-period crossover trial - Bingna Wang; Chen Huang; Lang Xu; Xihua Fu; Xiaojun Ma; Guoxing You; Jianfen Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Dynamic HGI trajectories and their impact on survival in patients with sepsis: a machine learning prognostic model - Aifeng He; Wei Jiang; Jing Fu; Leiming Xu; Congliang You; Suhui Li; Jiangquan Yu; Ruiqiang Zheng (Inflammation Research, 2025)

Sustainable utilization of bayer red mud in asphalt materials: Multiscale performance enhancement mechanisms and economic feasibility evaluation - Tao Fu; Haoze Zhang; Feng Qin; Huiming Bao; Duo Wu; You Cheng; Haicheng Ai (Journal of Cleaner Production, 2025)

Associations of PFOA and PFOS exposure with liver injury: Evidence from Two Population Studies and integrative adverse outcome pathway analysis - Yingqian You; Xin Guan; Hui Zhao; Tianhao Wu; Chenming Wang; Yang Xiao; Yuhan Zhou; Shiru Hong; Ye Fu; Meian He; Huan Guo (Environmental Pollution, 2025)

Pretrain-finetune neural operator for multi-fidelity surrogate modeling of structural dynamic systems - Pei-Lin Li; Shi-Fu Liu; Yi-Qing Ni; Jian-Ming Ling; You-Wu Wang (Engineering Structures, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

On-chip single-cell mass spectrometry for streamlined metabolic exploration enabled by a reversibly-bonded microfluidic platform - Jiacheng You; Anqi Chen; Jianxiong Qiu; Yaling Ye; Chongchong Mei; Guanghou Fu; Baiye Jin; Luhong Wen (Analytica Chimica Acta, 2025)

Plastic film mulching ensures maize climate resilience: A perspective of temperature suitability and optimal sowing period window - Jing Wang; Ling Zhao; Bao-Zhong Wang; Fei Mo; Ning Wang; Shu-Tong Liu; Yuan Song; Ai-Tian Ren; Fu-Jian Mei; Yang Wang; Qi Lu; You-Cai Xiong (Soil and Tillage Research, 2025)

Axial compressive behavior of four-opening concrete filled sandwich steel tube (FCFSST) stub columns - Yu-Qin Zhang; You-Fu Yang; Feng Fu (Engineering Structures, 2025)

Astragaloside IV-PESV facilitates pyroptosis by enhancing palmitoylation of GSDMD protein mediated by ZDHHC1 - Xujun You; Honghan Li; Qixin Li; Qing Zhang; Yiguo Cao; Wei Fu; Bin Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Cosmetic potential of agar oligosaccharides: anti-melanogenesis and photoprotective effects - Lei Wang; Fengqi Yang; Xiaoting Fu; Young-Sang Kim; Xin Gao; You-Jin Jeon (Algal Research, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Mechanisms and effects of the digital economy on agricultural modernization: A sustainable development perspective - Yinghui Li; Xing You; Junzhi Fu; WenJing Zhou (Journal of Environmental Management, 2025)

Magnetic effervescence-assisted salting-out liquid-liquid extraction enables fast and effortless determination of pyrethroid insecticide residues in fresh fruits and herbal plants - Zhifei Fu; Xinyue Wang; Jinqing You; Wenxuan Li; Lifeng Han; Liming Wang; Di Chen (Food Chemistry, 2025)

Land use optimization for future ecosystem service demands: A case study in the Yanhe watershed - Yumian Zhang; Xutong Wu; Shuai Wang; You Zhou; Fengyu Fu; Nan Lu; Longbin Kou (Journal of Cleaner Production, 2025)

Weakening plasticulture boosts maize productivity while improving environmental benefits in drying east African Plateau - Fu-Jian Mei; Qing-Hui Wen; Yang Wang; Alex Ndolo Munyasya; Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Wei Wang; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; You-Cai Xiong (Journal of Cleaner Production, 2025)

Contributions of natural and anthropogenic factors to summertime thermal environments across different urban scales: An investigation in Chengdu-Chongqing agglomeration, China - Yangtao Wan; Song Yang; Han Han; Yao Mao; Xiao Liu; Meizi You; Xuecheng Fu; Junqing Tang; Ali Cheshmehzangi; Leila Mohaghegh Zahed; Bao-Jie He (Environmental Impact Assessment Review, 2025)

Incorporating zinc coordination driven nanozyme into chitosan and hyaluronic acid based nanoplatform for scavenging H2S/ROS in managing inflammatory bowel disease - Jiafeng Zou; Wenxing Ding; You Chen; Xier Pan; Xiuzhi Fu; Shulei Zheng; Yiting Lin; Chuanhe Xia; Ying Ma; Xiaochun Zhang; Shuang Wu; Feng Gao (Carbohydrate Polymers, 2025)

Exploring AI-enhanced NMR dereplication analysis for complex mixtures and its potential use in adulterant detection - Xiao-Nan Du; You-Wen Chen; Qing Wang; Hui-Ying Yang; Yong Lu; Xian-Fu Wu (Phytochemistry Reviews, 2025)

Niche differentiation shaped the evolution of rhizobacterial antibiotic resistance in paddy fields: Evidences from spatial-temporal and chemical-biological scaling - Yi Xu; Tinghong Fu; Guoxiang You; Shihong Yang; Songqi Liu; Wanyong Huang; Dengyun Peng; Jiahao Ji; Jianwei Zhang; Jie Zhang; Jun Hou (Journal of Hazardous Materials, 2025)

Alveolar surfactant-mimicking inhaled biomimetic nanovaccine with alveolar macrophage-targeting property potentiates anti-mpox immunity - Bin Li; Jiamei Wang; Judun Zheng; Wei Wang; Lingjie He; Yan Yan; Xinting Fu; Xingjie You; Man Gu; Han Duan; Yue Jia; Qin Gu; et al. (Chemical Engineering Journal, 2025)

Bioinspired structural laminates with superior ice-repellence and damage resistance for aviation applications - Mingdi Shi; You Pan; Haixiao Cao; Yongxin Guo; Xue Sun; Yuan Fu; Yihang Wu; Yufei Luo; Yangyu Lu; Zhenting Wu; Liang Jiang; Bo Li; et al. (Chemical Engineering Journal, 2025)

Development and Application of Blasting Vibration Prediction Model - Hongchao Li; Haoxuan Han; Shenglin Li; Greg You; Jun Fu; Zhengrong Li; Xiyao Wang (Rock Mechanics and Rock Engineering, 2025)

Characterizing the clustered landslides triggered by extreme rainfall during the 2024 typhoon Gaemi in Zixing City, Hunan Province, China - Hao Ma; Fawu Wang; Zijin Fu; Youqian Feng; Qi You; Sen Li (Landslides, 2025)

Forest conversion and root trenching reshape microbial functions regulating root litter decomposition and soil carbon dynamics - Lixia Wang; Shuangjia Fu; Haoying Gao; Huichao Li; Yang Liu; Lin Xu; Li Zhang; Han Li; Chengming You; Sining Liu; Hongwei Xu; Bo Tan; et al. (Applied Soil Ecology, 2025)

Human presence in the southeastern Tibetan Plateau after the Last Glacial Maximum - Jia-Jing Wang; Pei-Yang Tan; Yue Feng; Zhe-Xuan Zheng; Yu-Jie Guo; Jia-Ning He; You-Ping Wang; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

An N-heterocyclic carbene-copper(I) functionalized metal-organic framework: Synthesis and recoverable applications in the carboxylation of CO2 with terminal alkynes - Li-Xin You; Tian-Cheng Han; Jin-Rong Li; Jie Guo; Gang Xiong; Fu ding; Ya-Guang Sun (Journal of Environmental Chemical Engineering, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Method for planning subarea emission reduction strategies to improve ozone over a large area: A case of Taiwan - Tu-Fu Chen; Xin-Li Gong; Chang-You Tsai; Ken-Hui Chang (Atmospheric Environment, 2025)

Distribution, origins, impact factors and ecological risks of metallic elements in the sediment from Changhua River estuary, Hainan Island, China - Jiyong Ma; You Gou; Zeheng Chen; Kaizhe Fu; Dongming Wu; Dayu Bian; Jianhua Guo; Shiyou Zhang; Zhuang Xing; Dongxu Jiang (Frontiers in Marine Science, 2025)
Within the framework of global biogeochemical cycles, estuaries function as a critical interface that connects terrestrial and marine ecosystems. We assessed the heavy metal pollution risk in the Changhua River estuary area. The assessment focused on pollution characteristics, spatial distribution, and ecological risks, while also identifying potential origins of metallic elements through the application of correlation analysis, principal component analysis (PCA), and Positive Matrix Factorization (PMF) models. The results showed that: (1) Sediments were predominantly sandy and weakly alkaline properties, with significant spatial heterogeneity in metallic concentrations. The concentration of metals, compared to their background values (BVs), could be ranked as: Nearshore: Pb > As > Cd > Cu > Zn > Hg > Ni > Cr; Inshore: Cd > Hg > Pb > Zn > Cu > As > Ni > Cr; Estuary: Pb > Cd > Hg > Cu > Zn > Ni > Cr. Particularly, Cd and Hg in inshore sediments registered a mean concentration surpassing their BVs by 417.95% and 187.33%, respectively. (2) The sampling locations presented varying levels of ecological risk. Moderate ecological risk (150 ≤ RI < 300) accounted for 24.14% of the sites, primarily located in inshore and estuarine areas, while extreme ecological risk (300≤RI) was observed in 6.90% of the sites, concentrated within inshore regions. Hg and Cd were identified as the most hazardous metals. (3) Regarding metallic sources, Hg mainly originated from coal burning, while Pb, Zn, and Cd were likely linked to anthropogenic activities associated with port operations. In contrast, Cr, Ni, and Cu were primarily derived from natural and agricultural sources, and As was mainly associated with the residual accumulation of fertilizers and herbicides. Overall, human activities, including agriculture, aquaculture, and port transport, are the primary origins of metallic contamination in the estuarine sediments. Effective management and regular monitoring of port activities are essential for the governance of the estuarine environment. Such practices can yield valuable insights for continuous risk analysis, thereby supporting the ecological health and resilience of these vital environments.

New Colorimetric Chemosensor for Rapid Naked-Eye Detection of Cu2+ and Its Application in Gas-Generating Agents - Xiaohong Cheng; Jun You; Shaoyong Meng; Wenjie Shen; Tao Du; Wenbin Fu; Yunqiang Luo; Song Wang (Journal of Fluorescence, 2025)

Genetic assessment of feed efficiency in the spotted Babylon Babylonia areolata - Linwei Nie; Yijie Kong; Ziyi Ma; Jingqiang Fu; Shengtai Liu; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2025)

Benzo[a]pyrene exposure and incident risks of digestive system cancers: Insights from nested case-control studies and adverse outcome pathway network analysis - Hui Zhao; Yang Xiao; Ye Fu; Xin Guan; Ming Fu; Chenming Wang; Yuhan Zhou; Shiru Hong; Yingqian You; Yuxi Wang; Shengli Chen; Yichi Zhang; et al. (Journal of Hazardous Materials, 2025)

Impacts of sulfamethoxazole on heterotrophic nitrification-aerobic denitrification bacteria and its response strategies: Insights from physiology to proteomics - Teng-Fei Ma; Xiao-Yao Yu; Chong-Yang Xing; Hui-Min Fu; Hao-Yang Duan; You-Peng Chen (Journal of Environmental Management, 2025)

Physiological and proteomic insights into silver nanoparticle-induced stress responses and resistance mechanisms in aerobic denitrifying Enterobacter cloacae HNR - Teng-Fei Ma; Hong-Xi Ma; Chong-Yang Xing; Hui-Min Fu; Yu Shen; You-Peng Chen; Xiang-Yang Wei (Journal of Environmental Chemical Engineering, 2025)

Atypical absorption response to the trans-thylakoid electric field in the acidothermophilic red algae Cyanidioschyzon merolae and Galdieria partita - Guan-Lin Wu; Shin-Ying Tzeng; Benjamin Bailleul; Julien Sellés; You-Yuan Zhang; Han-Yi Fu (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2025)

Deciphering the roles of cellular and extracellular non-coding RNAs in chemotherapy-induced cardiotoxicity - Pan Feng; Fan Yang; Dongmei Zang; Dapeng Bai; Liyan Xu; Yueyun Fu; Ranran You; Tao Liu; Xinyu Yang (Molecular and Cellular Biochemistry, 2025)

N-doped carbon nanotubes encapsulated Ni3ZnC0.7 nanoparticles catalyst for peroxymonosulfate activation: Heterojunction structure and N-doping enhance electron transfer capability - Qihao Sun; Huiyuan Deng; Na Zhao; Junjie You; Zhicheng Pan; Bo Xing; Yuling Ye; Bo Lai; Xinye Yang; Xinjie Wang; Yunhui Lu; Jian Li; et al. (Chemosphere, 2025)

Development of a sex-specific molecular marker reveals the ZW/ZZ sex-determination system in Babylonia areolata (link 1807) - Yu Zou; Yuan Liang; Xuan Luo; Weiwei You; Minghui Shen; Jingqiang Fu; Caihuan Ke (Aquaculture, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Transcriptional and molecular simulation analysis of the response mechanism of anammox bacteria to 3,4-dimethylpyrazole phosphate stress - Cui-Zhong Chen; Jin Wang; Yi-Cheng Wang; Hui-Min Fu; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Hazardous Materials, 2025)

Experimental behaviour of four-opening concrete filled sandwich steel tube (FCFSST) beam-columns under lateral cyclic loading - Dong-Jie Zhang; You-Fu Yang; Feng Fu (Engineering Structures, 2025)

Olanzapine exposure disordered lipid metabolism, gut microbiota and behavior in zebrafish (Danio rerio) - Yawei Wang; Fu You; Zhenyi Huang; Yuan Liu; Boya Yang; Xulu Chang; Guokun Yang; Xue Tian; Shikun Feng; Xiaolin Meng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Potential roles of quorum quenching in microbial aggregates during wastewater treatment - Yi Fu; Song-Ya Li; Yang Chen; You-Peng Chen; Jin-Song Guo; Shao-Yang Liu; Peng Yan (Bioresource Technology, 2025)

A laboratory study on wave Attenuation by oyster reefs-mangrove system - Beihan Jiang; Chenming Fu; Tuofu You; Yuanmin Sun; Xiaohe Lai; Feng Cai; Zhaoyang Hu; Xinqiang Wang; Liang Chen; Yitan Lin; Chunling Pan (Geo-Marine Letters, 2025)

Straw incorporating in shallow soil layer improves field productivity by impacting soil hydrothermal conditions and maize reproductive allocation in semiarid east African Plateau - Sylvia Ngaira Indoshi; Wesly Kiprotich Cheruiyot; Muhammad Maqsood Ur Rehman; Fu-Jian Mei; Qing-Hui Wen; Alex Ndolo Munyasya; Kiprotich Koskei; David Mwehia Mburu; Aggrey Bernard Nyende; Levis Kavagi; Delphine Nyanchera Gisacho; Eliyas Feyisa Sori; et al. (Soil and Tillage Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Nondestructive three-dimensional structure and growth characteristics of anammox granular sludge - Meng-Wen Peng; Ya-Song Chen; You-Peng Chen; Wan Sun; Meng-Meng Liu; Xun Weng; Shuai Wang; Yu Shen; Hui-Min Fu (International Biodeterioration & Biodegradation, 2025)

Alcogels based on secalin and konjac glucomannan composites for the controlled release of curcumin - Linzhi Jing; Lingshan Su; Qingtong Xie; Shunjiang Zeng; Xianjian Zeng; Siyong You; Caili Fu; Jie Sun; Dejian Huang (Food Research International, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

Early Cretaceous dinosaur, bird and turtle tracks from the Lanzhou-Minhe Basin, Gansu Province, Northwest China - Lida Xing; Daqing Li; Qiyan Chen; Junyan Fu; Chunyong Chou; Lijun Zhang; Wenze You; Kexin Shi; Hendrik Klein (Cretaceous Research, 2025)

Study on excitation effect of different combination modes of shear wave vibroseis - Zhengtao You; Zhiqiang Huang; Lei Hao; Gang Li; Mingwei Fu; Ruohao Wang; Jun Shuai (Acta Geophysica, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Unraveling the resistance mechanism of anammox granular sludge to iron nanoparticles - Xun Weng; Meng-Jiao Gao; Zheng Mao; Hui-Min Fu; Shi-Jun Li; Peng Yan; You-Peng Chen (Journal of Environmental Management, 2025)

Multiscale revelation of asphalt morphology and adhesion performance evolution during stress relaxation process - Fu Xu; Jing Deng; Yizhou Liu; Huijun Xie; Zhengwu Long; Botao Dai; Hao Yang; Lingyun You; Chongzheng Zhu; Dongzhao Jin (Fuel, 2025)

Health impacts of climate resilient city development: Evidence from China - Kai-yang Fu; Yu-zhe Liu; Xin-yu Lu; Bin Chen; You-hua Chen (Sustainable Cities and Society, 2024)

A mixed layer height parameterization in a 3-D chemical transport model: Implications for gas and aerosol simulations - Hyeonmin Kim; Rokjin J. Park; Song-you Hong; Do-Hyeon Park; Sang-Woo Kim; Yujin J. Oak; Xu Feng; Haipeng Lin; Tzung-May Fu (Science of The Total Environment, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Exceptionally-fast antimony removal by hollow rod assembly of Fe@MnO2 nanosheets: Sequential utilization as aqueous alkaline battery anode - Tong Jiang; Guiyao Wu; You Fu; Yao Wang; Siqinhaolu Hao; Die Shao; Nianyi Xie; Ying Guo; Xinyue Zhang; Hongbin Sun (Journal of Environmental Chemical Engineering, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Fe-MOF derived Fe3O4/C-based hydrogel for efficient solar-driven photothermal evaporation - You Zhou; Lei Xu; Sheng-Jie Han; Cai-Hua Liu; Yi-Bin Li; Ming-Lai Fu; Baoling Yuan (Desalination, 2024)

Hybrid silicon dioxide–carbon nanotube superhydrophobic surfaces: Great wear resistance and excellent de-icing capability - Guanyi Li; Qigang Han; Kaibo Yang; Yulai Song; Siwei Fu; Yang You (Chemical Engineering Journal, 2024)

Emerging developments and applications of Zr-fumarate MOF membranes for sustainable environmental separations - Mao Fu; Chuanhui Chen; Shuai Zhang; Yuhua You; Huifang Zhao; Bin Lin; Shi-Qiang Wang; Yingchao Dong (Chemical Engineering Journal, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

In-situ fabrication of defect rich Cu2+1O on electrodeposited Cu cone arrays for promoting electrocatalytic anode hydrogen production - Yanhong Weng; Huanhua You; Danni Liu; Hao Chen; Hao Lin; Guodong Fu; Fengzhan Si; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (Chemical Engineering Journal, 2024)

Multi-output prediction for TBM operation parameters based on stacking ensemble algorithm - Yu Tang; Junsheng Yang; Yuyang You; Jinyang Fu; Xiangcou Zheng; Cong Zhang (Tunnelling and Underground Space Technology, 2024)

A pair of cadinane-type sesquiterpene enantiomers and other chemical constituents from the whole plants of Chloranthus henryi - Meng-Li He; Lian-Lian Xu; Shi-Qin Fu; Yang Liu; Yong-Ming Luo; Fang-You Chen (Biochemical Systematics and Ecology, 2024)

Characteristics and ozone formation potentials of volatile organic compounds in a heavy industrial urban agglomeration of Northeast China - Yue Zhang; Bo You; Yijing Shang; Qiuyang Bao; Yanli Zhang; Xiaobing Pang; Li Guo; Jing Fu; Weiwei Chen (Air Quality, Atmosphere & Health, 2024)

Mitochondrial DNA copy number mediated the associations between perfluoroalkyl substances and breast cancer incidence: A prospective case-cohort study - Yue Feng; Yingqian You; Mengying Li; Xin Guan; Ming Fu; Chenming Wang; Yang Xiao; Meian He; Huan Guo (Science of The Total Environment, 2024)

Sodic adakitic granites in the East Kunlun Orogen, China: Partial melting of ultrahigh-pressure metamorphic terranes during continental collision - Lei Qin; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Li-Qun Dai; Gang Wen; You-Shan Xia; Yao Zhou (Chemical Geology, 2024)

Influence of DOC of vacuum preloading on dynamic consolidation for dredged slurry - Jianchu Li; You Zhou; Hongtao Fu; Shuxiang Ye; Cien Pan; Liangjie Cai; Ying Cai; Bingeng Wang; Ye Zhang; Xiaobing Li (Marine Georesources & Geotechnology, 2024)

Novel compounds of Djulis ( Chenopodium formosanum Koidz ) increases collagen, antioxidants, inhibits adipogenesis - Yuan-You Lin; Yung-Kai Lin; Yung-Hsiang Lin; Chi-Fu Chiang (Natural Product Research, 2024)

In situ formation of solidified supramolecular solvent based dispersive liquid-liquid microextraction for the enrichment of phenylurea herbicides in water, fruit juice, and milk - Shurong Chen; Yuhao Jiang; Junxian Li; Meng You; Rongxu Zhang; Jilong Li; Zhuang Fu; Jiahan Xie; Zhibing Wang (Food Chemistry, 2024)

Atmospheric water demand dominates terrestrial ecosystem productivity in China - You Tu; Xiaofeng Wang; Jitao Zhou; Xiaoxue Wang; Zixu Jia; Jiahao Ma; Wenjie Yao; Xinrong Zhang; Zechong Sun; Pingping Luo; Xiaoming Feng; Bojie Fu (Agricultural and Forest Meteorology, 2024)

Two new diarylheptanoids from the green walnut husks of Juglans mandshurica Maxim. - Yuan-Yuan Zhou; Ning-Yu Liu; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Qi-Feng Fu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2024)

A practical equation for predicting saturated hydraulic conductivity of fine-grained soils - You Gao; Kaibin Sun; Shuo Wang; Jiwei Li; Dean Sun; Yuchen Fu (Journal of Hydrology, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Alleviating binary toxicity of polystyrene nanoplastics and atrazine to Chlorella vulgaris through humic acid interaction: Long-term toxicity using environmentally relevant concentrations - Mehdi Khoshnamvand; Dongmei You; Yafang Xie; Yixiao Feng; Marriya Sultan; De-Sheng Pei; Ailing Fu (Chemosphere, 2024)

Presence of humic acid in the environment holds promise as a potential mitigating factor for the joint toxicity of polystyrene nanoplastics and herbicide atrazine to Chlorella vulgaris: 96-H acute toxicity - Mehdi Khoshnamvand; Dongmei You; Yafang Xie; Yixiao Feng; Marriya Sultan; Xingyi Wei; Jingli Li; Ailing Fu; De-Sheng Pei (Chemosphere, 2024)

Effects of erythromycin on biofilm formation and resistance mutation of Escherichia coli on pristine and UV-aged polystyrene microplastics - Xiaofeng Han; Long Fu; Jing Yu; Kunting Li; Ziqing Deng; Ruihao Shu; Dali Wang; Jing You; Eddy Y. Zeng (Water Research, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Expansion-flow-modulated 3D printing of vertically aligned graphene photofuel cell - Chunjing Zhang; Xiangyu Qiao; Yihan You; Zhao He; Yifan Wang; Ping Li; Yongyi Zhang; Huili Fu; Zhengpeng Yang (Chemical Engineering Journal, 2024)

Biosynthetic potential of uncultured anammox community bacteria revealed through multi-omics analysis - Yi-Cheng Wang; Hui-Min Fu; Yu Shen; Jin Wang; Nuo Wang; You-Peng Chen; Peng Yan (Bioresource Technology, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

The impact of elevated CO2 concentration on photosynthesis, growth and hydraulics of evergreen and deciduous tree seedlings from a subtropical forest in Southwest China - Pei-Li Fu; Ya Zhang; Jin-Hua Qi; Yong-Jiang Zhang; Guang-You Hao; Patrick M. Finnegan; Qiao-Shun Yan; Ze-Xin Fan (Agricultural and Forest Meteorology, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

A new substrate equalization method for optimizing the influent conditions and fluid flow patterns of a multifed upflow anaerobic sludge blanket reactor with mature anammox granules - Bao-Shan Xing; Xi-Fang Tang; Ling-Hu Li; Yu-Lin Fu; Jia-Yi Liu; Ya-Ge Wang; Xin-Xin Sun; Yu-You Li; Rong Chen; Ren-Cun Jin (Bioresource Technology, 2024)

Survival and immune responses of two populations of Babylonia areolata and their hybrids under pathogenic Vibrio challenge - Jingqiang Fu; Yuan Liang; Minghui Shen; Wengang Lü; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2024)

Identifying sensitive precursors of ozone formation using photochemical indicators and transition values comprised by continuous automatic monitoring data - Chang-You Tsai; Tu-Fu Chen; Ken-Hui Chang (Atmospheric Environment, 2024)

Concentrated fireworks display-induced changes in aerosol vertical characteristics and atmospheric pollutant emissions - Lingjian Duanmu; Weiwei Chen; Li Guo; Jing Fu; Bo You; Hongwu Yang; Tianshu Zhang (Atmospheric Environment, 2024)

Robust augmented estimation for hourly PM$$_{2.5}$$ using heteroscedastic spatiotemporal models - Yanan Song; Jinran Wu; Liya Fu; You-Gan Wang (Stochastic Environmental Research and Risk Assessment, 2024)

Motility behavior and physiological response mechanisms of aerobic denitrifier, Enterobacter cloacae strain HNR under high salt stress: Insights from individual cells to populations - Meng Cheng; Hui-Min Fu; Zheng Mao; Peng Yan; Xun Weng; Teng-Fei Ma; Xiao-Wei Xu; Jin-Song Guo; Fang Fang; You-Peng Chen (Science of The Total Environment, 2024)

DNA methylation aging signatures of multiple metals exposure and their mediation effects in metal-associated mortality: Evidence from the Dongfeng-Tongji cohort study - Chenming Wang; Guorong Zhong; Chenliang Liu; Shiru Hong; Xin Guan; Yang Xiao; Ming Fu; Yuhan Zhou; Yingqian You; Tianhao Wu; Hui Zhao; Yuxi Wang; et al. (Journal of Hazardous Materials, 2024)

Ni-CaO-CaZrO3 bi-functional materials for high purity hydrogen production via sorption enhanced steam reforming of ethanol - Yinxiang Wang; Hui Zhou; Dingding Yao; Gianni Olguin; Haixia Ding; Boyu Qu; Wensheng Xie; Zegang Fu; You Guo; Xin Wang; Aimin Li; Guozhao Ji (Journal of Cleaner Production, 2024)

Enhanced removal of Cd2+ from water by a bacterioferritin from Candidatus Kuenenia stuttgartiensis within engineering bacteria - Jin Wang; Cui-Zhong Chen; Yi-Cheng Wang; Hui-Min Fu; Peng Yan; You-Peng Chen (Chemical Engineering Journal, 2024)

Benzethonium chloride affects short chain fatty acids produced from anaerobic fermentation of waste activated sludge: Performance, biodegradation and mechanisms - Fengyuan You; Mengge Tang; Jiamin Zhang; Dongbo Wang; Qizi Fu; Jiangfu Zheng; Boqun Ye; Yintong Zhou; Xiaoming Li; Qi Yang; Xuran Liu; Abing Duan; et al. (Water Research, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Lanostane triterpenoids from the fruiting bodies of Ganoderma amboinense - Li Yang; Guan-Hai Dong; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; You-Gen Wu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Comparing the mechanisms of syntrophic volatile fatty acids oxidation and methanogenesis recovery from ammonia stress in regular and biochar-assisted anaerobic digestion: Different roads lead to the same goal - Gaojun Wang; Peng Fu; Yan Su; Bo Zhang; Mengyuan Zhang; Qian Li; Jianfeng Zhang; Yu-You Li; Rong Chen (Journal of Environmental Management, 2024)

Biochar’s role to achieve multi-pathway nitrogen removal in anammox systems: Insights from electron donation and selective microbial enrichment - Jingwei Fu; Qian Li; Mawuli Dzakpasu; Yifei He; Pengyu Zhou; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Deploying photovoltaic arrays in degraded grasslands is a promising win-win strategy for promoting grassland restoration and resolving land use conflicts - Bin Zhang; Ruohui Zhang; You Li; Shiwen Wang; Minghui Zhang; Fu Xing (Journal of Environmental Management, 2024)

Achieving tunable time-dependent delayed emission color via dynamic competition between the matrix and carbon dots for anti-counterfeiting and multidimensional encryption - Yufeng Chang; Nian Fu; Mingjun Chen; You Zhang; Fuxing Li; Zhenyang Liu; Fenghe Wang; Gang Yue; Xu Li; Li Guan (Chemical Engineering Journal, 2024)

Functions and values of sulfated polysaccharides from seaweed - D. P. Nagahawatta; N. M. Liyanage; Thilina U. Jayawardena; Fengqi Yang; H. H. A. C. K. Jayawardena; M. J. M. S. Kurera; Fahe Wang; Xiaoting Fu; You-Jin Jeon (Algae, 2023)
Sulfated polysaccharides (SPs) isolated from seaweed have emerged as remarkable bioactive compounds with a wide spectrum of biological activities and have substantial value in the scientific and industrial domains. The current study explores the diverse biological activities of SPs and their relationship with their structures. This aids in an in-depth examination of the multifaceted biological activities of SPs, including anticoagulant, anti-inflammatory, antiviral, antioxidant, and immunomodulatory properties, which underpin their potential health benefits. Furthermore, the current study explores the complicated properties of SPs, with their extraction methodologies and techniques for precise characterization. Elucidation of the commercial significance of SPs derived from brown, red, and green seaweed by highlighting their potential applications has emphasized their importance in human well-being. Further, this review emphasizes the challenges needed to overcome research and industrial innovations for SPs. Collaboration among researchers, industry stakeholders, and regulatory authorities can overcome these challenges and elevate the potential of SPs to revolutionize industries such as pharmaceuticals, cosmeceuticals, food, and biotechnology.

Targeted degradation of naphthalene by peroxymonosulfate activation using molecularly imprinted biochar - Xueji You; Chaomeng Dai; Zeyu Wang; Yanping Duan; Jun Bo Zhang; Xiaoying Lai; Jiajun Hu; Jixiang Li; Maisideke Maimaitijiang; Yalei Zhang; Shuguang Liu; Rongbing Fu (Chemosphere, 2023)

Unraveling the mysteries of (L)WY-domain oomycete effectors - Hongyuan Zheng; Liyuan You; Shuaijie Meng; Daowen Wang; Zhengqing Fu (Science Bulletin, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Monazite and titanite U Pb ages of granitoids from the North Qinling Terrane: Implications for the subduction of the Shangdan Ocean and accretionary processes - Zheng-wei Qin; Wolfgang Siebel; Jian-ming Fu; Hao Wang; Bo Bao; Yu-shuai Yu; Liang Shan; You-yue Lu; Yuan-Bao Wu (Lithos, 2023)

Fate of iron nanoparticles in anammox system: Dissolution, migration and transformation - Xun Weng; Hui-Min Fu; Zheng Mao; Peng Yan; Xiao-Wei Xu; Yu Shen; You-Peng Chen (Journal of Environmental Management, 2023)

Metal-organic frameworks (MOFs)-derived Mn2SnO4@C anode based on dual lithium storage mechanism for high-performance lithium-ion capacitors - You-Kang Duan; Zhi-Wei Li; Shi-Chun Zhang; Tong Su; Yan-Fang Ma; Ai-Jun Jiao; Zhen-Hai Fu (Chemical Engineering Journal, 2023)

16s-RNA sequencing analysis of the influence of UV radiation on the metabolic pathways of pollutants in the A2O process - Y. W. Li; J. H. You; Y. C. Zong; J. Wang; C. H. Fu (International Journal of Environmental Science and Technology, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Lithium isotope systematics and water/rock interactions in a shallow-water hydrothermal system at Milos Island, Greece - U-Tat Lou; Shein-Fu Wu; Chen-Feng You; Chuan-Hsiung Chung; Eugenia Valsami-Jones; Emmanuel Baltatzis (Marine Chemistry, 2023)

How to utilize neighborship: The role of residents' social capital in the neighborhood renewal in China - Ruopeng Huang; Guiwen Liu; Kaijian Li; Asheem Shrestha; Xinyue Fu; Kairui You; Xun Deng (Environmental Impact Assessment Review, 2023)

Plume effects on Martian surface: Revealing evolution characteristics of plume-surface interaction at Tianwen-1 landing site - Pengwei Luo; Xiaoping Zhang; Renrui Liu; Mingjie Zhang; Cunhui Li; Yi Xu; Roberto Bugiolacchi; Baocheng Hua; Haiyan Zhang; Liansheng Li; Jilin You; Yanyan Xu; et al. (Engineering Geology, 2023)

Biochar facilitates methanogens evolution by enhancing extracellular electron transfer to boost anaerobic digestion of swine manure under ammonia stress - Gaojun Wang; Peng Fu; Bo Zhang; Ji Zhang; Qiuyi Huang; Gaofei Yao; Qian Li; Mawuli Dzakpasu; Jianfeng Zhang; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

Calcium-dependent protein kinases CPK21 and CPK23 phosphorylate and activate the iron-regulated transporter IRT1 to regulate iron deficiency in Arabidopsis - Zhangqing Wang; Yanting Zhang; Yisong Liu; Dali Fu; Zhang You; Panpan Huang; Huiling Gao; Zhenqian Zhang; Cun Wang (Science China Life Sciences, 2023)

The Critical Role of Equilibrative Nucleoside Transporter-2 in Modulating Cerebral Damage and Vascular Dysfunction in Mice with Brain Ischemia-Reperfusion - Hui-Ling Chiang; Kuo-Chen Wu; You-Yin Chen; Chin-Jui Ho; Han-Lin Wang; Yu-Hua Fu; Wen-Yu Chen; Chun-Jung Lin (Pharmaceutical Research, 2023)

Resource utilization of rice straw to prepare biochar as peroxymonosulfate activator for naphthalene removal: Performances, mechanisms, environmental impact and applicability in groundwater - Jun Bo Zhang; Chaomeng Dai; Zeyu Wang; Xueji You; Yanping Duan; Xiaoying Lai; Rongbing Fu; Yalei Zhang; Maisideke Maimaitijiang; Kah Hon Leong; Yaojen Tu; Zhi Li (Water Research, 2023)

Two-point-one-line modularized strategy combined with Holliday-junction button probes for multiloci SNPs long-range distribution analysis - Wang Luo; You Wu; Xueping Chen; Li Zhang; Li Wang; Dan Bai; Qian Liu; Ting Wang; Hongyan Yu; Yaxing Xie; Yixin Fu; Zhongzhong Wang; et al. (Chemical Engineering Journal, 2023)

Efficient 2-O-α-D-glucopyranosyl-sn-glycerol production by single whole-cell biotransformation through combined engineering and expression regulation with novel sucrose phosphorylase from Leuconostoc mesenteroides ATCC 8293 - Peifeng Duan; Mengfei Long; Xian Zhang; Zuyi Liu; Jiajia You; Xuewei Pan; Weilai Fu; Meijuan Xu; Taowei Yang; Minglong Shao; Zhiming Rao (Bioresource Technology, 2023)

Plant facilitation improves carbon production efficiency while reducing nitrogen input in semiarid agroecosystem - Wei Wang; Meng-Ying Li; Shuang-Guo Zhu; Aziz Khan; Xiu-Ping Tao; Guang-Fu Huang; Hai-Ying Liu; Wei Zhang; Hong-Yan Tao; Dong-Shan Gong; Chao Song; You-Cai Xiong (CATENA, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

Two lanostane triterpenoids with α -glucosidase inhibitory activity from the fruiting bodies of Ganoderma weberianum - De Xian Kong; Qing Yun Ma; Li Yang; Qing Yi Xie; Chun Ying Deng; Hao Fu Dai; Yan Hua; You Xing Zhao (Natural Product Research, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

ED-DQN: An event-driven deep reinforcement learning control method for multi-zone residential buildings - Qiming Fu; Zhu Li; Zhengkai Ding; Jianping Chen; Jun Luo; Yunzhe Wang; You Lu (Building and Environment, 2023)

Supplementation with Akkermansia muciniphila improved glucose metabolism disorder in common carp (Cyprinus carpio L.) - Guokun Yang; Aixia Jiang; Huimin Cai; Fu You; Shengkui Wu; Yanmin Zhang; Xindang Zhang; Yawei Shen; Xulu Chang; Wenpan Hu; Keke Li; Xiaolin Meng (Aquaculture, 2023)

Bioactivated and selective: A promising new family of nematicides with a novel mode of action - Liyuan You; Di Wu; Ruize Zhang; Daowen Wang; Zheng Qing Fu (Molecular Plant, 2023)

Effects of adding different ratios of residual sludge and food waste co-anaerobic fermentation liquid to AAO wastewater treatment process - Junhao You; Shilong Tang; Yongchen Zong; Hongtao Shan; Jun Wang; Chunhui Fu (Journal of Water Process Engineering, 2023)

Recent soybean subsidy policy did not revitalize but stabilize the soybean planting areas in Northeast China - Yuanyuan Di; Nanshan You; Jinwei Dong; Xiaoyong Liao; Kaishan Song; Ping Fu (European Journal of Agronomy, 2023)

Unraveling the structure and function of bacterioferritin in Candidatus Kuenenia stuttgartiensis: Iron storage sites maintain cellular iron homeostasis - Jin Wang; Que Wang; Yu-Jiao Tang; Hui-Min Fu; Fang Fang; Jin-Song Guo; Peng Yan; You-Peng Chen (Water Research, 2023)

Two new α-pyrone derivatives from sponge-derived fungus Curvularia sp. ZYX-Z-4 - Qing-Hui Yan; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Ying Fu; You-Xing Zhao (Phytochemistry Letters, 2023)

Dominant anatase TiO2 (0 0 1) with rich surface hydroxyls as catalytic active sites for selective catalytic oxidation of cyclohexylamine to cyclohexanone oxime - Wenjin Ni; Dejian Yan; Shangjun Fu; Yanan Wei; Hongyun Yang; Xiaowen Zhang; Fangfang Zhao; Kuiyi You; He'an Luo (Chemical Engineering Journal, 2023)

Transient Receptor Potential Mucolipin-1 Participates in Intracerebral Hemorrhage-Induced Secondary Brain Injury by Inducing Neuroinflammation and Neuronal Cell Death - Jinzhao Shi; Xiang Li; Jiasheng Ding; Jinrong Lian; Yi Zhong; Haiying Li; Haitao Shen; Wanchun You; Xi’an Fu; Gang Chen (NeuroMolecular Medicine, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Long-term effects of phosphorus deficiency on one-stage partial nitrification-anammox system and recovery strategies - Liang Zhang; Zhe Tian; Yunzhi Qian; Fuqiang Chen; Yu-You Li; Xueke Wang; Cuilian Fu; Yongzhi Chi (Journal of Cleaner Production, 2023)

Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles - Ke Zhang; Qing Chen; Jie Xiao; Lijun You; Siming Zhu; Chao Li; Xiong Fu (Food Hydrocolloids, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

One positive part of copper ion on biocatalysts: CNPs@Cu-Trypsin-assisted aqueous extraction technique for simultaneous exploration of edible insect oil and protein - Jin-Zheng Wang; Cheng-Kun Wu; Xin-Ying Wang; Yuan-Zhi Xu; Richard Ansah Herman; Sheng Sheng; Shuai You; Jun Wang; Fu-An Wu (Chemical Engineering Journal, 2023)

Hollow MnO2-Based Nanoprobes for Enhanced Photothermal/Photodynamic /Chemodynamic Co-Therapy of Hepatocellular Carcinoma - Bei Li; Xiwen Ye; Yi Fu; Lei Feng; Jianrong Xu; Xiaoya Niu; Hui Ye; Zhen You (Pharmaceutical Research, 2023)

Association of Adolescent Bullying Victimization with Meeting 24-hour Movement Behavior Recommendations: A Cross-Sectional Study Using the Combined 2015–2019 Youth Risk Behavior Survey - You Fu; Ryan D. Burns; Peng Zhang; Samantha Dyer; Nora Constantino (Journal of Science in Sport and Exercise, 2023)

Two new indole alkaloids isolated from a mangrove-derived fungus Colletotrichum sp. HD-1 - Dan He; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hong-Juan Zhu; Hao-Fu Dai; You-Gen Wu; Dong-Mei Yang; You-Xing Zhao (Phytochemistry Letters, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Mechanical deterioration effect and damage evolution characteristics of soft sandstone with different water-immersed heights under uniaxial compression - Han-Dong Liu; Shuai Liu; Hai-Ning Liu; Jia-Xing Chen; Zhi-Guo Xia; Ju-Yun Zhai; Yun-You Fu (Bulletin of Engineering Geology and the Environment, 2023)

Single aromatics sulfonamide substituted dibenzothiazole squaraines for tumor NIR imaging and efficient photodynamic therapy at low drug dose - Jun-Hui Li; Pei-Dan You; Fei Lu; Jun-Tao Huang; Jia-Luo Fu; Hao-Yun Tang; Chun-Qiong Zhou (Journal of Photochemistry and Photobiology B: Biology, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Associations between multiple metals exposure and biological aging: Evidence from the Dongfeng-Tongji cohort - Chenming Wang; Shiru Hong; Xin Guan; Yang Xiao; Ming Fu; Hua Meng; Yue Feng; Yuhan Zhou; Qiang Cao; Fangfang Yuan; Chenliang Liu; Guorong Zhong; et al. (Science of The Total Environment, 2023)

Effect of etching and reduction time on the structure, performance, and stability of GO-based membrane for water purification - Fan-xin Kong; Lian You; Jia-mei Cao; Qian Liu; Ping Xia; Jin-fu Chen (Journal of Environmental Chemical Engineering, 2023)

Evoking and enhancing ferroptosis of cancer stem cells by a liver-targeted and metal-organic framework-based drug delivery system inhibits the growth and lung metastasis of hepatocellular carcinoma - Pengfei Zhang; Junjie Fu; Jing Hu; Qingjun You; Xueyan Yao; Dong Hua; Jian Yin; Yong Mao (Chemical Engineering Journal, 2023)

Biochar-assisted anaerobic membrane bioreactor towards high-efficient energy recovery from swine wastewater: Performances and the potential mechanisms - Gaojun Wang; Guohao Liu; Gaofei Yao; Peng Fu; Changxi Sun; Yu Li; Qian Li; Yu-You Li; Rong Chen (Bioresource Technology, 2023)

In vitro and in vivo antioxidant activities of a fucose-rich fucoidan isolated from Saccharina japonica - Yueqi Kong; Lei Wang; You-Jin Jeon; Jiachao Xu; Xin Gao; Xiaoting Fu (Journal of Applied Phycology, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Microbial functional communities and the antibiotic resistome profile in a high-selenium ecosystem - Yanmei Sun; Jia Guo; Fu Wei; Xiaohui Chen; Meng Li; Chao Li; Size Xia; Guangming Zhang; Wencai You; Xin Cong; Tian Yu; Shiwei Wang (Chemosphere, 2023)

Clostridium butyricum-fermented Chinese herbal medicine enhances the immunity by modulating the intestinal microflora of largemouth bass (Micropterus salmoides) - Xiaolin Meng; Huimin Cai; Heng Li; Fu You; Aixia Jiang; Wenpan Hu; Keke Li; Xindang Zhang; Yanmin Zhang; Xulu Chang; Guokun Yang; Zhigang Zhou (Aquaculture, 2023)

Nonclimacteric ripening characteristics of ‘Jen-Ju Bar’ guava conferred by a defect in the expression of the system-2 ACC synthase gene PgACS1 - Kuo-En Chen; You-Fu Liu; Yu-Chang Liu; Margo Sulistio; Chyi-Chuann Chen; Chun-Ta Wu (Postharvest Biology and Technology, 2023)

Thermodynamic characteristics of methane hydrate formation in high-pressure microcalorimeter under different reaction kinetics - Juan Fu; Jia-Mei Mo; Shi-Jun Liu; Wen-Zhe Yi; Yi-Song Yu; Neng-You Wu; Xiao-Li Chen; Qiu-Cheng Su; Xiao-Sen Li (Fuel, 2023)

Multiple metals exposure and blood mitochondrial DNA copy number: A cross-sectional study from the Dongfeng-Tongji cohort - Ming Fu; Chenming Wang; Shiru Hong; Xin Guan; Hua Meng; Yue Feng; Yang Xiao; Yuhan Zhou; Chenliang Liu; Guorong Zhong; Yingqian You; Tianhao Wu; et al. (Environmental Research, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Experimental study on the effect of an oyster reef on the nonlinear characteristics of irregular waves - Beihan Jiang; Hui Zhang; Tuofu You; Yuanmin Sun; Chenming Fu; Weijie Liao; Feng Cai (Frontiers in Marine Science, 2022)
As a “marine ecological engineer”, the oyster reefs not only perform important ecological functions, but also reduce the damage caused by waves to protective structures such as seawalls. However, oyster reefs in shallow water change the nonlinear characteristics of waves and affect sediment transport and coastal evolution. Based on Fourier spectrum and analysis of Wavelet Transform, the influence of artificial bag oyster reefs on the energy and nonlinear phase coupling of irregular waves are studied through physical experiment. The results show that oyster reefs have a substantial effect on the energy of primary harmonic, which transfer to higher harmonics through triad interactions, and a considerable reduction in primary harmonic energy and an increase in higher harmonics energy are reflected in the energy spectra. The transmission spectrum behind the oyster reefs shows three peaks at primary, secondary and third harmonics. The bicoherence spectrum indicates that the peaks at secondary and third harmonics mainly result from the self-coupling of the primary harmonics and phase coupling between the primary and secondary harmonics respectively. As the water depth increases, the degree of nonlinear coupling between wave components decreases, which leads to the energy of wave components at different frequencies increases. With increasing top width, the length of the shoaling region increases, and the growth of triad nonlinear interactions are observed in wavelet-based bicoherence spectra, resulting in the spectral peak energy decreasing while the secondary harmonics energy increasing in the spectrum. Finally, the potential application of an ecological system composed by “oyster reefs + mangroves” is discussed. As the effect of water depth on wave energy is much greater than that of top width, in artificial oyster reef construction, it is recommended that keep the oyster reefs non-submerged in terms of wave dissipation. Further studies should take the dynamic growth effect of oyster reefs into account.

The Influence of DO on the Microbiological Community of the A2O Treatment of Municipal Wastewater in Alpine Regions - Mingzhe Guo; Jun Wang; Junhao You; Yongchen Zong; Chunhui Fu (Water, Air, & Soil Pollution, 2022)

The combined effect of titanium dioxide nanoparticles and cypermethrin on male reproductive toxicity in rats - Yuxin Li; Mingqing Zhong; Xianzhi He; Ruoyu Zhang; Yu Fu; Ruolan You; Feiyan Tao; Lei Fang; Yuanyuan Li; Qingfeng Zhai (Environmental Science and Pollution Research, 2022)

Phosphorus fractionation and adsorption characteristics in drinking water reservoir inlet river sediments under human disturbance - Zihao Fu; Zijin Hong; Junling Wei; Yukai Liao; Songlin You; Yifan Wang; Jianjing Lv; Huan Feng; Marek Kolenčík; Xuexiu Chang; Yu Qian (Journal of Soils and Sediments, 2022)

CHLNET: A novel hybrid 1D CNN-SVR algorithm for estimating ocean surface chlorophyll-a - Donglin Fan; Hongchang He; Ruisheng Wang; You Zeng; Bolin Fu; Yuankang Xiong; Lilong Liu; Yong Xu; Ertao Gao (Frontiers in Marine Science, 2022)
Developing a unified chlorophyll-a (Chla) inversion algorithm for cross-water types is a significant challenge owing to the insufficiency of input features and training samples. Although machine learning algorithms can build a consistent model for different trophic waters, the accuracy of the inversion is dependent on the quality of the extended features. Here, we designed a novel hybrid framework called CHLNET, which combines a one-dimensional convolutional neural network (1D CNN) and support vector regression (SVR). The 1D CNN is used to extract features from the original band features, and the SVR is used to perform a fit of Chla. CHLNET is trained and tested using match-up pairs of SeaWiFS remote sensing reflectance [Rrs(λ)] in situ with Chla ranging from 0.009 mg/m³ to 138.046 mg/m³, which covers mostly ocean water types. Performance metrics in the log space of CHLNET were better than those of the state-of-the-art algorithms on the testing dataset, and CHLNET had the best overall performance with the largest cover area in the star plot. The frequency distribution of predicted Chla by CHLNET was more consistent with that of in situ Chla. While the spatial pattern was not smooth in low Chla concentration waters, CHLNET demonstrated excellent mapping ability at the global and local scales in high Chla concentration waters. Through the band-shift method, which transfers the Rrs(λ) of MERIS and MODIS-Aqua to the Rrs(λ) of SeaWiFS in the visible spectral range, CHLNET obtained better accuracy than the blended algorithm of OCx and CI on MERIS and MODIS-Aqua matchups, which validates the generalization of CHLNET on cross-sensor types. The results indicate that CHLNET avoids the drawbacks of manually constructing extended features and the need for merging water type-appropriate algorithms for Chla retrieval, as well as provides a new idea for unified Chla concentration inversion across water types. Thus, CHLNET may serve as an alternative approach for Chla inversion.

Strength and structural variations in dredger fill subjected to vacuum dynamic consolidation - You Zhou; Hongtao Fu; Tian Jin; Mingfeng Li; Junfeng Ni (Marine Georesources & Geotechnology, 2022)

Awareness for Endoscopic Screening Among Accompanying Children of Hospitalized Esophageal Cancer Patients in Henan - Lian Qun Zhang; Xian Juan Du; Fu You Zhou; Pei Nan Chen; Hai Ling Wang; Li Sun; Xiu Ling Li (Journal of Cancer Education, 2022)

IL-38, a potential therapeutic agent for lupus, inhibits lupus progression - Wang-Dong Xu; Lin-Chong Su; Lu Fu; You-Yu Lan; Xiao-Yan Liu; Qi Huang; Qian Wu; Jie Zhou; An-Fang Huang (Inflammation Research, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Multi-Omics Study on the Molecular Mechanisms of Tetraodon Nigroviridis Resistance to Exogenous Vibrio Parahaemolyticus Infection - Shoujia Jiang; Lijun Fu; Zijian Gao; Hengwei Deng; Yong Zhang; Xinxin You; Qiong Shi; Danqi Lu (Frontiers in Marine Science, 2022)
Vibrio parahaemolyticus is an important marine pathogen that causes inflammation and even death in teleost fishes. It has brought significant economic losses to the aquaculture industry as well as high risks to the sustainable development of marine fisheries. In the present study, the fish Tetraodon nigroviridis and the bacterial pathogen Vibrio parahaemolyticus were used to explore the molecular mechanisms underlying the immune response of T. nigroviridis to V. parahaemolyticus exogenous infection. The microRNA (miRNA)–mRNA–protein omics and corresponding experimental validation, followed by comparative analysis, revealed several differentially expressed genes involved in various components of the immune system, including the following: complement system, chemokines, lysosomes, phagocytes, B-cell receptor signaling pathway, T-cell receptor signaling pathway, Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway, and phospholipid metabolism, among others. Especially, the complements component 3 (C3) gene and protein expression levels were significantly higher after V. parahaemolyticus infection, and miRNAs targeting C3, including mir-6089-y, mir-460-y, and mir-1584-x, were significantly down-regulated. The gene and protein expression levels of complement 1 subunit qA (C1qA) were significantly down-regulated, while mir-203 targeting C1qA was significantly up-regulated. Overall, four complement genes (C1qA, IG, C3, and C5) , which are key genes in the classical pathway of complement system activation for inflammatory response, were identified. Evolutionary analysis suggested that T. nigroviridis, acquired an increased ability to recognize pathogens by evolving a more complex complement system than terrestrial vertebrates. In addition, quantitative real-time polymerase chain reaction showed high consistency with the obtained multi-omics results, indicating the reliability of the sequencing data generated in the present study. In summary, our findings can serve as a fundamental basis for further in-depth multi-omics studies on the inflammatory processes of aquatic pathogens hindering fish sustainable production.

Correction to: Chitosan‑based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu‑Wei Huang; Fang‑Ching Yeh; You‑Ren Ji; Ying‑Fu Su; Ying‑shih Su; Ming‑Hsien Chiang; Shian‑Chiuan Tzeng; Chien‑Yao Fu; Aristine Cheng; Yung‑Chih Wang; Yi‑Tzu Lee (Drug Delivery and Translational Research, 2022)

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Geochemical characteristics and source of crude oil in the Shenhu uplift, Pearl River Mouth Basin, South China Sea - Xiaoyan Fu; Shijia Chen; Xin He; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

Identification of the vertical sealing of faults by geochemical methods—taking the Zhu-3 sub-basin of the Pearl River Mouth Basin as an example - Xiaoyan Fu; Shijia Chen; Junjun You; Hui Li; Mingzhu Lei (Arabian Journal of Geosciences, 2022)

Classification of ASD based on fMRI data with deep learning - Lizhen Shao; Cong Fu; Yang You; Dongmei Fu (Cognitive Neurodynamics, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Comparative physiological and proteomic analyses of mangrove plant Kandelia obovata under cold stress - Jiao Fei; You-Shao Wang; Hao Cheng; Fu-Lin Sun; Cui-Ci Sun (Ecotoxicology, 2021)

Bacterial community variations in the South China Sea driven by different chemical conditions - Fu-lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Zhao-Yu Jiang; Hao Cheng; Jiao Fei (Ecotoxicology, 2021)

Regulatory relationship between backfill mining and environmental engineering geological patterns induced by underground coal mining - Shiliang Liu; Weiguo Li; Guangsheng Fu; You Zhang; Xinghai Li; Bin Xie; Haodong Zhang; Wenhui Zhang (Arabian Journal of Geosciences, 2021)

Fast estimation method of volumes of landslide deposit by the 3D reconstruction of smartphone images - Lin Fu; Jun Zhu; Wei-lian Li; Ji-gang You; Zhang-yu Hua (Landslides, 2021)

Tracing Nutrients and Organic Matter Changes in Eutrophic Wenchang (China) and Oligotrophic Krka (Croatia) Estuaries: A Comparative Study - You-You Hao; Zhuo-Yi Zhu; Fu-Tao Fang; Tihana Novak; Milan Čanković; Enis Hrustić; Zrinka Ljubešić; Ming Li; Jin-Zhou Du; Rui-Feng Zhang; Blaženka Gašparović (Frontiers in Marine Science, 2021)
Estuaries modify the concentration and composition of riverine nutrients and organic matter (OM), which eventually determine the riverine flux effect to coasts. Nutrients, organic carbon (OC), pigments, and amino acids (AAs) from the samples collected in the eutrophic Wenchang River Estuary (WRE) in China and the oligotrophic Krka River Estuary (KRE) in Croatia were analyzed in order to have a better understanding of how estuaries regulate terrestrial materials. We found a clear increase of dissolved inorganic nitrogen (DIN) concentration and its subsequent decrease due to the removal of DIN (over 100 μM) in the WRE, whereas DIN showed minor variation lengthwise in the KRE, i.e., with the salinity changes, ranging between 1.0 and 5.8 μM. The elevated algae-derived OC, dissolved organic nitrogen, and particulate AAs nitrogen suggest that the OM assimilation may explain approximately one-third of the DIN removal in the WRE, whereas in the oligotrophic KRE, such inorganic to organic transformation is not likely to be significant. Due to the prominent estuarine nitrogen removal/assimilation process, DIN/dissolved inorganic phosphorus (DIP) ratio was as high as 425 in the upper WRE under strong riverine influence, but it declined to as low as 5.4 at the mouth of WRE, that is even lower than DIN/DIP ratio at the mouth of oligotrophic KRE (12). When compared with other rivers worldwide, the Wenchang River showed high nutrients and organic carbon yields. Given the contrasting estuarine process (e.g., DIN removal) between the KRE and the WRE, apparent high nutrient yield from eutrophic rivers should be viewed with caution in ocean studies as the final impact to coastal zone could be similar to the oligotrophic rivers like the KRE.

Talaromyces Marneffei Infection in an HIV-Negative Child with a CARD9 Mutation in China: A Case Report and Review of the Literature - Cheng-yan You; Fang Hu; Si-wei Lu; Dan-dan Pi; Feng Xu; Cheng-jun Liu; Yue-qiang Fu (Mycopathologia, 2021)

Chitosan-based hydrogels to treat hydrofluoric acid burns and prevent infection - Shu-Wei Huang; Fang-Ching Yeh; You-Ren Ji; Ying-Fu Su; Ying-shih Su; Ming-Hsien Chiang; Shian-Chiuan Tzeng; Chien-Yao Fu; Aristine Cheng; Yung-Chih Wang; Yi-Tzu Lee (Drug Delivery and Translational Research, 2021)

Budgets of rotational and divergent kinetic energy in the warm-sector torrential rains over South China: a case study - Shui-Xin Zhong; Wei-Guang Meng; Fu-You Tian (Meteorology and Atmospheric Physics, 2021)
The contributions of divergent and rotational wind components to the kinetic energy budget during a record-breaking rainstorm on 7 May 2017 over South China are examined. This warm-sector extreme precipitation caused historical maximum of 382.6 mm accumulated rainfall in 3 h over the Pearl River Delta (PRD) regions in South China. Results show that there was a high low-level southerly wind-speed tongue stretching into the PRD regions from the northeast of the South China Sea (SCS) during this extreme precipitation. The velocity potential exhibited a low-value center as well as a low-level divergence-center over the SCS. The rotational components of the kinetic energy (KR)-related terms were the main contribution-terms of the kinetic energy budget. The main contribution-terms of KR and the divergent component of kinetic energy (KD) were the barotropical and baroclinic processes-related terms due to cross-contour flow and the vertical flux divergence.

Fucoidan isolated from the popular edible brown seaweed Sargassum fusiforme suppresses lipopolysaccharide-induced inflammation by blocking NF-κB signal pathway - Lei Wang; Jae-Young Oh; Hye-Won Yang; Xiaoting Fu; Jae-Il Kim; You-Jin Jeon (Journal of Applied Phycology, 2021)

Correction to: Ortho-silicic Acid Inhibits RANKL-Induced Osteoclastogenesis and Reverses Ovariectomy-Induced Bone Loss In Vivo - Wenzheng Ma; Fu’an Wang; Yunhao You; Wenliang Wu; Hai Chi; Guangjun Jiao; Lu Zhang; Hongming Zhou; Hongliang Wang; Yunzhen Chen (Biological Trace Element Research, 2021)

Comparisons of Subjective and Objective Measures of Free-Living Daily Physical Activity and Sedentary Behavior in College Students - Ya-Wen Hsu; Chia-Chang Liu; Yen-Jung Chang; Yi-Ju Tsai; Wan-Chi Tsai; You Fu (Journal of Science in Sport and Exercise, 2021)

Enrichment and purification of red pigments from defective mulberry fruits using biotransformation in a liquid-liquid-solid three-phase system - Xue-Jiao Zhou; Chang-Tong Zhu; Lu-Yue Zhang; Shuai You; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2021)

Ortho-silicic Acid Inhibits RANKL-Induced Osteoclastogenesis and Reverses Ovariectomy-Induced Bone Loss In Vivo - Wenzheng Ma; Fu’an Wang; Yunhao You; Wenliang Wu; Hai Chi; Guangjun Jiao; Lu Zhang; Hongming Zhou; Hongliang Wang; Yunzhen Chen (Biological Trace Element Research, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

The ankyrin repeat-containing protein MdANK2B regulates salt tolerance and ABA sensitivity in Malus domestica - Fu-jun Zhang; Yin-huan Xie; Han Jiang; Xun Wang; Yu-Jin Hao; Zhenlu Zhang; Chun-Xiang You (Plant Cell Reports, 2021)

Application and Progress of Reinforcement Technology for Chinese Ancient Buildings with Wood Structure - Ru-yuan Yang; You-fu Sun; Xiao-feng Zhang (Geotechnical and Geological Engineering, 2020)

Geochemical constraints on the genesis of the Ekou banded iron formation, Shanxi Province, North China - Yekai Men; Ende Wang; Jianfei Fu; Sanshi Jia; Xinwei You; Qiangwen He (International Journal of Earth Sciences, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

New gravimetric-only and hybrid geoid models of Taiwan for height modernisation, cross-island datum connection and airborne LiDAR mapping - Cheinway Hwang; Hung-Jui Hsu; W. E. Featherstone; Ching-Chung Cheng; Ming Yang; Wenhsuan Huang; Chong-You Wang; Jiu-Fu Huang; Kwo-Hwa Chen; Chi-Hsun Huang; Hechin Chen; Wen-Yi Su (Journal of Geodesy, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

The class III peroxidase gene OsPrx24 is important for root Iron plaque formation and benefits phosphorus uptake in Rice plants under alternate wetting and drying irrigation - Xu-Jian Yang; You-Qiang Fu; Shuo Ma; Haihua Gan; Weifeng Xu; Hong Shen (Plant and Soil, 2020)

Inositol as a new enhancer for improving lipid production and accumulation in Schizochytrium sp. SR21 - Zhao-Xin Liu; Shuai You; Bin-Ping Tang; Bo Wang; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

Effect of the Resistance Exercise on Elementary School Students’ Physical Fitness - You Fu; Ryan D. Burns; Nora Constantino; Jim Fitzsimmons; Peng Zhang (Journal of Science in Sport and Exercise, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

Exogenous 24-Epibrassinolide Alleviates Effects of Salt Stress on Chloroplasts and Photosynthesis in Robinia pseudoacacia L. Seedlings - Jianmin Yue; Yanhuang You; Liang Zhang; Zhiyuan Fu; Jinping Wang; Jinchi Zhang; Robert D. Guy (Journal of Plant Growth Regulation, 2019)

Anti-oxidant and anti-inflammatory activities of ultrasonic-assistant extracted polyphenol-rich compounds from Sargassum muticum - Yuan Yu; Le Wang; Xiaoting Fu; Lei Wang; Xiaodan Fu; Min Yang; Zhenlian Han; Haijin Mou; You-Jin Jeon (Journal of Oceanology and Limnology, 2019)

Influences of soil moisture and salt content on loess shear strength in the Xining Basin, northeastern Qinghai-Tibet Plateau - Jiang-tao Fu; Xia-song Hu; Xi-lai Li; Dong-mei Yu; Ya-bin Liu; You-Qing Yang; Zhao-xin Qi; Shu-xia Li (Journal of Mountain Science, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Profiling of indole metabolic pathway in thermo-sensitive Bainong male sterile line in wheat (Triticum aestivum L.) - Qing Su; Jing Yang; Qing Yun Fu; Fei Yun Jia; Suo Ping Li; Yong Li; You Yong Li (Physiology and Molecular Biology of Plants, 2019)

Orientation Behavior and Regulatory Gene Expression Profiles in Migratory Agrotis ipsilon (Lepidoptera: Noctuidae) - Hong Chang; Jiang Long Guo; Xiao Wei Fu; You Ming Hou; Kong Ming Wu (Journal of Insect Behavior, 2019)

Ambient air particulates-bound metallic elements sources identifications during winter and summer at a Science Park - Guor-Cheng Fang; Chao-Yang Huang; Yuan-Jie Zhuang; Wen-Chuan Huang; Kai-Hsiang Tsai; You-Fu Xiao (Environmental Geochemistry and Health, 2018)

LC–MS/MS-Based Metabolome Analysis of Biochemical Pathways Altered by Food Limitation in Larvae of Ivory Shell, Babylonia areolata - Jingqiang Fu; Minghui Shen; Yawei Shen; Wengang Lü; Miaoqin Huang; Xuan Luo; Jinjin Yu; Caihuan Ke; Weiwei You (Marine Biotechnology, 2018)

Wet depositions of mercury during plum rain season in Taiwan - Guor-Cheng Fang; Wen-Chuan Huang; Yuan-Jie Zhuang; Chao-Yang Huang; Kai-Hsiang Tsai; You-Fu Xiao (Environmental Geochemistry and Health, 2018)

Scutellarin suppresses neuroinflammation via the inhibition of the AKT/NF-κB and p38/JNK pathway in LPS-induced BV-2 microglial cells - Pengtao You; San Fu; Kun Yu; Yu Xia; Hezhen Wu; Yanfang Yang; Chaozhi Ma; Dan Liu; Xin Chen; Jun Wang; Xiaochuan Ye; Yanwen Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Identification of Fusarium species associated with soybean root rot in Sichuan Province, China - Xiaoli Chang; Hao Dai; Duiping Wang; Huanhuan Zhou; Wanqin He; Yao Fu; Faisal Ibrahim; You Zhou; Guoshu Gong; Jing Shang; Jizhi Yang; Xiaoling Wu; et al. (European Journal of Plant Pathology, 2018)

Review of total suspended particles (TSP) and PM2.5 concentration variations in Asia during the years of 1998–2015 - Guor-Cheng Fang; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; You-Fu Xiao; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2018)

Characterization and expression of lin-28a involved in lin28/let-7signal pathway during early development of P. olivaceus - Yuanshuai Fu; Lina Gao; Zhiyi Shi; Feng You; Junling Zhang; Wenjuan Li (Fish Physiology and Biochemistry, 2018)

Levels of PCDD/Fs, PBDEs, and PBDD/Fs in Breast Milk from Southern Taiwan - Men-Wen Chen; Bryan Angelo A. Castillo; Din-Yan Lin; How-Ran Chao; Lemmuel L. Tayo; Yan-You Gou; Fu-An Chen; Kuo-Lin Huang (Bulletin of Environmental Contamination and Toxicology, 2018)

Ensemble evaluation and projection of climate extremes in China using RMIP models - Xiaorui Niu; Shuyu Wang; Jianping Tang; Dong‐Kyou Lee; William Gutowski; Koji Dairaku; John McGregor; Jack Katzfey; Xuejie Gao; Jia Wu; Song‐you Hong; Yuqing Wang; et al. (International Journal of Climatology, 2018)
Under the framework of the Regional Climate Model Intercomparison Project (RMIP III), simulation results from six regional climate models (RCMs) and two global climate models (GCMs) were used to generate climate extreme indices for the present and future over China using two ensemble methods. All the models reasonably captured the observed climate extremes, and performance‐based ensemble averaging (PEA) outperformed the individual model and equal‐weighted averaging (MME) for the control climate. However, noticeable cold deficiencies in temperature extremes were found over areas with complex topography, and too frequent heavy precipitation at smaller intensities was simulated using the multiple model ensembles. Under the A1B scenario for 2041–2060, widespread increases in the 90th percentiles of the maximum temperatures (Tmax90p) and the 10th percentile of the minimum temperatures (Tmin10p) were projected, with larger increases in winter than in summer. Greater intensities in precipitation extremes were projected over China, with the exception of Inner Mongolia. Large uncertainties exist in the projected mean diurnal temperature range (Trange), number of days with precipitation exceeding 10 mm (R10) and the maximum number of consecutive dry days (CDD) because of disagreements in both the magnitudes and signs of the climate model projections, and even the two ensemble methods presented opposite signs over some regions.

OsGLO4 is involved in the formation of iron plaques on surface of rice roots grown under alternative wetting and drying condition - Xiao-Li Yu; Dao-Ming Wu; You-Qiang Fu; Xu-Jian Yang; František Baluška; Hong Shen (Plant and Soil, 2018)

Concentrations and analysis of health risks of ambient air metallic elements at Longjing site in central Taiwan - Guor-Cheng Fang; Yu-Cheng Chen; Chaur-Tsuen Lo; Meng-Hsien Cho; Yuan-Jie Zhuang; Kai-Hsiang Tsai; Chao-Yang Huang; You-Fu Xiao (Environmental Geochemistry and Health, 2018)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Optimized decellularization protocol including α-Gal epitope reduction for fabrication of an acellular porcine annulus fibrosus scaffold - Lien-Chen Wu; Yi-Jie Kuo; Fu-Wen Sun; Chia-Hsien Chen; Chang-Jung Chiang; Pei-Wei Weng; Yang-Hwei Tsuang; Yi-You Huang (Cell and Tissue Banking, 2017)

Annual ambient atmospheric mercury speciation measurement from Longjing, a rural site in Taiwan - Guor-Cheng Fang; Chaur-Tsuen Lo; Meng-Hsien Cho; Yuan-Jie Zhuang; Kai-Hsiang Tsai; Chao-Yang Huang; You-Fu Xiao (Environmental Geochemistry and Health, 2017)

PM2.5 particulates and metallic elements (Ni, Cu, Zn, Cd and Pb) study in a mixed area of summer season in Shalu, Taiwan - Guor-Cheng Fang; You-Fu Xiao; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2017)

Simple additive simulation overestimates real influence: altered nitrogen and rainfall modulate the effect of warming on soil carbon fluxes - Xiangyin Ni; Wanqin Yang; Zemin Qi; Shu Liao; Zhenfeng Xu; Bo Tan; Bin Wang; Qinggui Wu; Changkun Fu; Chengming You; Fuzhong Wu (Global Change Biology, 2017)
Experiments and models have led to a consensus that there is positive feedback between carbon (C) fluxes and climate warming. However, the effect of warming may be altered by regional and global changes in nitrogen (N) and rainfall levels, but the current understanding is limited. Through synthesizing global data on soil C pool, input and loss from experiments simulating N deposition, drought and increased precipitation, we quantified the responses of soil C fluxes and equilibrium to the three single factors and their interactions with warming. We found that warming slightly increased the soil C input and loss by 5% and 9%, respectively, but had no significant effect on the soil C pool. Nitrogen deposition alone increased the soil C input (+20%), but the interaction of warming and N deposition greatly increased the soil C input by 49%. Drought alone decreased the soil C input by 17%, while the interaction of warming and drought decreased the soil C input to a greater extent (−22%). Increased precipitation stimulated the soil C input by 15%, but the interaction of warming and increased precipitation had no significant effect on the soil C input. However, the soil C loss was not significantly affected by any of the interactions, although it was constrained by drought (−18%). These results implied that the positive C fluxes–climate warming feedback was modulated by the changing N and rainfall regimes. Further, we found that the additive effects of [warming × N deposition] and [warming × drought] on the soil C input and of [warming × increased precipitation] on the soil C loss were greater than their interactions, suggesting that simple additive simulation using single‐factor manipulations may overestimate the effects on soil C fluxes in the real world. Therefore, we propose that more multifactorial experiments should be considered in studying Earth systems.

Umbilical cord-derived mesenchymal stem cell transplantation for treating elderly vascular dementia - Yan He; Xingfang Jin; Jun Wang; Mingyao Meng; Zongliu Hou; Weimeng Tian; You Li; Wenju Wang; Yunhong Wei; Yipeng Wang; Hongqiong Meng; Xuyang Lu; et al. (Cell and Tissue Banking, 2017)

Patterns of SSR variation in bread wheat (Triticum aestivum L.) seeds under ex situ genebank storage and accelerated ageing - Yong-Bi Fu; Mo-Hua Yang; Carolee Horbach; Dallas Kessler; Axel Diederichsen; Frank M. You; Hong Wang (Genetic Resources and Crop Evolution, 2017)

Seasonal variations and sources study by way of back trajectories and ANOVA for ambient air pollutants (particulates and metallic elements) within a mixed area at Longjing, central Taiwan: 1-year observation - Guor-Cheng Fang; Chaur-Tsuen Lo; Yuan-Jie Zhuang; Meng-Hsien Cho; Chao-Yang Huang; You-Fu Xiao; Kai-Hsiang Tsai (Environmental Geochemistry and Health, 2017)

Redistribution of Cav2.1 channels and calcium ions in nerve terminals following end-to-side neurorrhaphy: ionic imaging analysis by TOF–SIMS - Chiung-Hui Liu; Hung-Ming Chang; To-Jung Tseng; Chyn-Tair Lan; Li-You Chen; Su-Chung Youn; Jian-Jr Lee; Fu-Der Mai; Jui-Feng Chou; Wen-Chieh Liao (Histochemistry and Cell Biology, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Piromelatine ameliorates memory deficits associated with chronic mild stress-induced anhedonia in rats - Wan Fu; Heng Xie; Moshe Laudon; Shouhong Zhou; Shaowen Tian; Yong You (Psychopharmacology, 2016)

Mechanism of Rock Burst Occurrence in Specially Thick Coal Seam with Rock Parting - Jian-chao Wang; Fu-xing Jiang; Xiang-jun Meng; Xu-you Wang; Si-tao Zhu; Yu Feng (Rock Mechanics and Rock Engineering, 2016)

Identification, separation and component analysis of reddish brown and non-reddish brown iron plaque on rice (Oryza sativa) root surface - You-Qiang Fu; Xu-Jian Yang; Zhi-Hong Ye; Hong Shen (Plant and Soil, 2016)

Estrogenic effects in the influents and effluents of the drinking water treatment plants - Yan-You Gou; Susana Lin; Danielle E. Que; Lemmuel L. Tayo; Ding-Yan Lin; Kuan-Chung Chen; Fu-An Chen; Pen-Chi Chiang; Gen-Shuh Wang; Yi-Chyuan Hsu; Kuo Pin Chuang; Chun-Yu Chuang; et al. (Environmental Science and Pollution Research, 2016)

Quantitative measurement of Parkinsonian gait from walking in monocular image sequences using a centroid tracking algorithm - Sheng-Huang Lin; Shih-Wei Chen; Yu-Chun Lo; Hsin-Yi Lai; Chich-Haung Yang; Shin-Yuan Chen; Yuan-Jen Chang; Chin-Hsing Chen; Wen-Tzeng Huang; Fu-Shan Jaw; You-Yin Chen; Siny Tsang; et al. (Medical & Biological Engineering & Computing, 2016)

QTL mapping of flag leaf traits in common wheat using an integrated high-density SSR and SNP genetic linkage map - Qiuhong Wu; Yongxing Chen; Lin Fu; Shenghui Zhou; Jiaojiao Chen; Xiaojie Zhao; Dong Zhang; Shuhong Ouyang; Zhenzhong Wang; Dan Li; Guoxin Wang; Deyun Zhang; et al. (Euphytica, 2016)

An AhR-Luciferase Adenovirus Infection System for Rapid Screening of Dioxins in Soils - Cherng-Gueih Shy; How-Ran Chao; Ding-Yan Lin; Yan-You Gou; Chun-Yu Chuang; Kuo Pin Chuang; Chih-Cheng Chen; Yung-Chun Hsiao; Fu-An Chen (Bulletin of Environmental Contamination and Toxicology, 2016)

Overexpression of d-amino acid oxidase from Bradyrhizobium japonicum, enhances resistance to glyphosate in Arabidopsis thaliana - Hongjuan Han; Bo Zhu; Xiaoyan Fu; Shuanghong You; Bo Wang; Zhenjun Li; Wei Zhao; Rihe Peng; Quanhong Yao (Plant Cell Reports, 2015)

Exogenous transglutaminase improves multiple-stress tolerance in Lactococcus lactis and other lactic acid bacteria with glutamine and lysine in the cell wall - Yu Li; Zhipeng Kan; Yuanli You; Xueling Gao; Zhigeng Wang; Ruiyan Fu (Biotechnology Letters, 2015)

Soil geochemistry changes induced by a foreign soil reconstruction project in Three Gorges Reservoir region of China - Juan Liu; Chao-Fu Wei; You-Jin Luo; Jing Du (Journal of Mountain Science, 2015)

Spatial and vertical distribution of bacterial community in the northern South China Sea - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Cui-Ci Sun; Hao Cheng (Ecotoxicology, 2015)

Spinal cord projections to the cerebellum in the mouse - Gulgun Sengul; YuHong Fu; You Yu; George Paxinos (Brain Structure and Function, 2015)

Gene expression profile of Arabidopsis under sodium bisulfite treatment by oligo-microarray analysis - Bo Zhu; Shuang-Hong You; Hong-Juan Han; Xiao-Yan Fu; Wei Zhao; Jian-Jie Gao; Yong Xue; Ri-He Peng; Quan-Hong Yao (Acta Physiologiae Plantarum, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

A measurement of summertime dry deposition of ambient air particulates and associated metallic pollutants in Central Taiwan - Guor-Cheng Fang; Hung-Che Chiang; Yu-Cheng Chen; You-Fu Xiao; Chia-Ming Wu; Yu-Chen Kuo (Environmental Geochemistry and Health, 2015)

The assessment of high recharge areas using DO indicators and recharge potential analysis: a case study of Taiwan’s Pingtung plain - Jui-Pin Tsai; Yu-Wen Chen; Liang-Cheng Chang; Wen-Fu Chen; Chung-Jung Chiang; You-Cheng Chen (Stochastic Environmental Research and Risk Assessment, 2015)

Characterization and high expression of recombinant Ustilago maydis xylanase in Pichia pastoris - Hongjuan Han; Shuang You; Bo Zhu; Xiaoyan Fu; Baihui Sun; Jin Qiu; Chengye Yu; Lei Chen; Rihe Peng; Quanhong Yao (Biotechnology Letters, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Anther development of maize (Zea mays) and longstamen rice (Oryza longistaminata) revealed by cryo-SEM, with foci on locular dehydration and pollen arrangement - Chih-Hua Tsou; Ping-Chin Cheng; Chiung-Maan Tseng; Hsiao-Jung Yen; Yu-Lan Fu; Tien-Rong You; David B. Walden (Plant Reproduction, 2015)

Integrated risk assessment method of waterlog disaster in Huaihe River Basin of China - Ju-Liang Jin; Juan Fu; Yi-Ming Wei; Shang-Ming Jiang; Yu-Liang Zhou; Li Liu; You-Zhen Wang; Cheng-Guo Wu (Natural Hazards, 2015)

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

The Correlation Between Dielectric Properties and Microstructure of Femoral Bone in Rats with Different Bone Qualities - Feng Tao; Feng Fu; Fusheng You; Zhenyu Ji; Jun Wen; Xuetao Shi; Xiuzhen Dong; Min Yang (Annals of Biomedical Engineering, 2014)

Spatial structure of eukaryotic ultraplankton community in the northern South China Sea - Zhao-Yu Jiang; You-Shao Wang; Fu-Lin Sun (Biologia, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

The physiological mechanism of enhanced oxidizing capacity of rice (Oryza sativa L.) roots induced by phosphorus deficiency - You Qiang Fu; Xu Jian Yang; Hong Shen (Acta Physiologiae Plantarum, 2014)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Association between CYP1A1 polymorphisms and esophageal cancer: a meta-analysis - Fang-Fang Shen; Fu-You Zhou; Qi-Si Xue; Ying Pan; Lu Zheng; Hua Zhang; Li-Dong Wang; Hou-Feng Zheng (Molecular Biology Reports, 2013)

Microbial community shift with decabromodiphenyl ether (BDE 209) in sediments of the Pearl River estuary, China - Peng Wu; You-Shao Wang; Cui-Ci Sun; Fu-Lin Sun; Yu-Tu Wang (Biologia, 2013)

Outline of Occupational Chromium Poisoning in China - Yuan Yang; Hong Liu; Xian-hong Xiang; Fu-you Liu (Bulletin of Environmental Contamination and Toxicology, 2013)

Construction of an integrated genetic map based on maternal and paternal lineages of tea (Camellia sinensis) - Chih-Yi Hu; Tair-Chyang Lee; Hsien-Tsung Tsai; You-Zen Tsai; Shun-Fu Lin (Euphytica, 2013)

Reduced expression of aquaporin 9 in tubal ectopic pregnancy - Yin Fen Ji; Li You Chen; Kai Hong Xu; Ji Fen Yao; Yi Fu Shi; Xue Jun Shanguan (Journal of Molecular Histology, 2013)

A novel dirigent protein gene with highly stem-specific expression from sugarcane, response to drought, salt and oxidative stresses - Guo Jin-long; Xu Li-ping; Fang Jing-ping; Su Ya-chun; Fu Hua-ying; Que You-xiong; Xu Jing-sheng (Plant Cell Reports, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Effects of three different PAHs on nitrogen-fixing bacterial diversity in mangrove sediment - Fu-Lin Sun; You-Shao Wang; Cui-Ci Sun; Ya-Lan Peng; Chao Deng (Ecotoxicology, 2012)

Basin-scale groundwater response to precipitation variation and anthropogenic pumping in Chih-Ben watershed, Taiwan - Kuo-Chin Hsu; Hsin-Fu Yeh; You-Cheng Chen; Cheng-Haw Lee; Chung-Ho Wang; Feng-Sheng Chiu (Hydrogeology Journal, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Overexpression of a vacuolar H+-pyrophosphatase and a B subunit of H+-ATPase cloned from the halophyte Halostachys caspica improves salt tolerance in Arabidopsis thaliana - You-zhen Hu; You-ling Zeng; Bo Guan; Fu-chun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Rank regression analysis of correlated water quality data from South East Queensland - You-Gan Wang; Liya Fu (Environmental and Ecological Statistics, 2011)

A high-frequency cyclic secondary somatic embryogenesis system for Cyclamen persicum Mill - Cui Rong You; Ting Jun Fan; Xue Qin Gong; Fu Hua Bian; Li Kun Liang; Fu Ning Qu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Gas sand distribution prediction by prestack elastic inversion based on rock physics modeling and analysis - Fu-Bang He; Jun You; Kai-Yuan Chen (Applied Geophysics, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Inflammatory bowel disease unclassified - Ning Zhou; Wei-xing Chen; Shao-hua Chen; Cheng-fu Xu; You-ming Li (Journal of Zhejiang University-SCIENCE B, 2011)

Identification of differentially expressed transcripts involved in the salt-stress response of Salsola ferganica by suppression subtractive hybridization - Bo Guan; Gang-qiang Jiang; Ying-xin Wang; Zhi-cai Wang; Yakupjan Haxim; Qian Bao; You-zhen Hu; Fu-chun Zhang; Yan Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

A spontaneous high expression of heat shock cognate 70 (HSC 70) in zebrafish Danio rerio larvae arising from tissue-specific translation of preexisting mRNA - Lung-Yin Hsu; Fu-Lung Yeh; Tun-Yuan Cheng; You-Hsin Chang; Shiu-Mei Liu; Todd Hsu (Fisheries Science, 2010)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Effect of Dietary Polyphenon E and EGCG on Lung Tumorigenesis in A/J Mice - Qi Zhang; Huijing Fu; Jing Pan; Jun He; Seto Ryota; Yukihiko Hara; Yian Wang; Ronald A Lubet; Ming You (Pharmaceutical Research, 2010)

Comparison of Three Kinds of Electrode–Skin Interfaces for Electrical Impedance Scanning - Yinsuo Yin; Zhenyu Ji; Wen Zhang; Nan Wang; Feng Fu; Ruigang Liu; Fusheng You; Xuetao Shi; Xiuzhen Dong (Annals of Biomedical Engineering, 2010)

Fractionated evaluation of immunohistochemical hormone receptor expression enhances prognostic prediction in breast cancer patients treated with tamoxifen as adjuvant therapy - Ching-hung Lin; Huang-chun Lien; Fu-chang Hu; Yen-shen Lu; Sung-hsin Kuo; Ling-chu Wu; San-lin You; Ann-lii Cheng; King-jen Chang; Chiun-sheng Huang (Journal of Zhejiang University-SCIENCE B, 2010)

Application of Electrical Impedance Tomography for Continuous Monitoring of Retroperitoneal Bleeding After Blunt Trauma - Wanjun Shuai; Fusheng You; Hongyi Zhang; Wei Zhang; Feng Fu; Xuetao Shi; Ruigang Liu; Tingyi Bao; Xiuzhen Dong (Annals of Biomedical Engineering, 2009)

Effect of UV-B radiation on the growth and antioxidant enzymes of Antarctic sea ice microalgae Chlamydomonas sp. ICE-L - Quan-fu Wang; Yan-hua Hou; Jin-lai Miao; Guang-you Li (Acta Physiologiae Plantarum, 2009)

Novel electrode–skin interface for breast electrical impedance scanning - Zhenyu Ji; Xiuzhen Dong; Xuetao Shi; Fusheng You; Feng Fu; Ruigang Liu (Medical & Biological Engineering & Computing, 2009)

Substitutions of 169Lys and 173Thr in nonstructural protein 1 influence the infectivity and pathogenicity of XJ-160 virus - Wu-yang Zhu; Yi-liang Yang; Shi-hong Fu; Li-hua Wang; You-gang Zai; Qing Tang; Guo-dong Liang (Archives of Virology, 2009)

Association of angiotensin-converting enzyme and endothelial Nitric Oxide synthase gene polymorphisms with vascular disease in ESRD patients in a Chinese population - Feng-Ying Tang; Fu-You Liu; Xiong-Wei Xie (Molecular and Cellular Biochemistry, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Cloning and characterization of phosphorus starvation inducible Brassica napus PURPLE ACID PHOSPHATASE 12 gene family, and imprinting of a recently evolved MITE-minisatellite twin structure - Kun Lu; You-Rong Chai; Kai Zhang; Rui Wang; Li Chen; Bo Lei; Jun Lu; Xin-Fu Xu; Jia-Na Li (Theoretical and Applied Genetics, 2008)

Aldehyde volatiles emitted in succession from mechanically damaged leaves of poplar cuttings - Zeng-hui Hu; Ying-bai Shen; You-qing Luo; Fan-yi Shen; Hai-bo Gao; Rong-fu Gao (Journal of Plant Biology, 2008)

Chymase induces profibrotic response via transforming growth factor-β1/Smad activation in rat cardiac fibroblasts - Xiao-Yan Zhao; Lian-You Zhao; Qiang-Sun Zheng; Jin-Lin Su; Hao Guan; Fu-Jun Shang; Xiao-Lin Niu; Yan-Ping He; Xiao-Long Lu (Molecular and Cellular Biochemistry, 2008)

Purification and characterization of a psychrophilic glutathione reductase from Antarctic ice microalgae Chlamydomonas sp. Strain ICE-L - Yu Ding; Jin-Lai Miao; Quan-Fu Wang; Zhou Zheng; Guang-You Li; Ji-Chang Jian; Zao-He Wu (Polar Biology, 2007)

Analysis of wheat-Thinopyrum intermedium derivatives with BYDV-resistance - Zhi-Shan Lin; Zhi-Fu Cui; Xiang-Yan Zeng; You-Zhi Ma; Zeng-Yan Zhang; Toshiki Nakamura; Goro Ishikawa; Kazuhiro Nakamura; Hisashi Yoshida; Zhi-Yong Xin (Euphytica, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Localization of vesicular glutamate transporters in the peripheral vestibular system of rat - Yuan Wang; You-Wang Pang; Yu-Lin Dong; Fu-Xing Zhang; Jin-Lian Li; Yun-Qing Li (Neuroscience Bulletin, 2007)

Facial pain induces the alteration of transient receptor potential vanilloid receptor 1 expression in rat trigeminal ganglion - Lei Pei; Chuan-You Lin; Jia-Pei Dai; Guang-Fu Yin (Neuroscience Bulletin, 2007)

The Heilongjiang Group: A Jurassic accretionary complex in the Jiamusi Massif at the western Pacific margin of northeastern China - Fu‐Yuan Wu; Jin‐Hui Yang; Ching‐Hua Lo; Simon A. Wilde; De‐You Sun; Bor‐Ming Jahn (Island Arc, 2007)
The tectonic setting of the Eastern Asian continental margin in the Jurassic is highly controversial. In the current study, we have selected the Heilongjiang complex located at the western margin of the Jiamusi Massif in northeastern China for geochronological investigation to address this issue. Field and petrographic investigations indicate that the Heilongjiang complex is composed predominately of granitic gneiss, marble, mafic‐ultramafic rocks, blueschist, greenschist, quartzite, muscovite‐albite schist and two‐mica schist that were tectonically interleaved, indicating they represent a mélange. The marble, two‐mica schist and granitic gneiss were most probably derived from the Mashan complex, a high‐grade gneiss complex in the Jiamusi Massif with which the Heilongjiang Group is intimately associated. The ultramafic rocks, blueschist, greenschist and quartzite (chert) are similar to components in ophiolite. The sensitive high mass‐resolution ion microprobe U‐Pb zircon age of 265 ± 4 Ma for the granitic gneiss indicates that the protolith granite was emplaced coevally with Permian batholiths in the Jiamusi Massif. 40 Ar/ 39 Ar dating of biotite and phengite from the granitic gneiss and mica schist yields a late Early Jurassic metamorphic age between 184 and 174 Ma. Early components of the Jiamusi Massif, including the Mashan complex, probably formed part of an exotic block from Gondwana, affected by late Pan‐African orogenesis, and collided with the Asian continental margin during the Early Jurassic. Subduction of oceanic crust between the Jiamusi block and the eastern part of the Central Asian Orogenic Belt resulted in the formation of a huge volume of Jurassic granites in the Zhangguangcai Range. Consequently, the collision of the Jiamusi Massif with the Central Asian Orogenic Belt to the west can be considered as the result of circum‐Pacific accretion, unrelated to the Central Asian Orogenic Belt. The widespread development of Jurassic accretionary complexes along the Asian continental margin supports such an interpretation.

The displacement computation and construction pre-control of a foundation pit in Shanghai utilizing FEM and intelligent methods - You-Liang Chen; Rafig Azzam; Fu-Bo Zhang (Geotechnical and Geological Engineering, 2006)

Benzo[a]pyrene-induced cell cycle progression is through ERKs/cyclin D1 pathway and requires the activation of JNKs and p38 mapk in human diploid lung fibroblasts - Hong Ju Du; Ning Tang; Bing Ci Liu; Bao Rong You; Fu Hai Shen; Meng Ye; Ai Gao; Chuan Shu Huang (Molecular and Cellular Biochemistry, 2006)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Heterologous Expression and Purification of Recombinant Allophycocyanin in Marine Streptomyces sp. Isolate M097 - Yan-Hua Hou; Song Qin; You-Xun Li; Fu-Chao Li; Huan-Zhang Xia; Fang-Qing Zhao (World Journal of Microbiology and Biotechnology, 2006)

Expression of CspA and GST by an Antarctic psychrophilic bacterium Colwellia sp. NJ341 at near-freezing temperature - Quan-Fu Wang; Jin-Lai Miao; Yan-Hua Hou; Yu Ding; Guang-You Li (World Journal of Microbiology and Biotechnology, 2006)

Purification and Characterization of a Cold-active Iron Superoxide Dismutase from a Psychrophilic Bacterium, Marinomonas sp. NJ522 - Zhou Zheng; Ying-Hui Jiang; Jin-Lai Miao; Quan-Fu Wang; Bo-Tao Zhang; Guang-You Li (Biotechnology Letters, 2006)

Purification and Characterization of an Extracellular Cold-Active Serine Protease from the Psychrophilic Bacterium Colwellia sp. NJ341 - Quan-Fu Wang; Jin-Lai Miao; Yan-Hua Hou; Yu Ding; Guo-Dong Wang; Guang-You Li (Biotechnology Letters, 2005)

Impact of oil field exploitation on eco-environment of the Daqing lakes - Shao-peng Yu; Jin-fu Lu; Guang-you Sun (Chinese Geographical Science, 2003)

Concept, distribution law and formation machanism of inland saline-alkaline wetland - Guang-you Sun; Xin-zheng Luo; Fu-ke Yi; Xiao-ping Zhang (Chinese Geographical Science, 2000)